Stage-structured plastisphere succession sustains antibiotic resistomes on microplastics during full-scale A2/O wastewater treatment - Xin Hou; Xiaoran Li; Yunan Lin; Xiaoyan Li; Wen Li; Lei Zhang; Jiamin Li; Ziming Jiang; Sen Wang; Xiaotong Wang; Xianhua Liu (Water Research, 2027)

A probabilistic pedotransfer function for estimating the soil water characteristic curve and quantifying its uncertainty - Xin-Yuan Wang; He-Fu Pu; Ming Min; Yu Miao; Sen-Lin Xie; Xiao He (Computers and Geotechnics, 2027)

Elucidating the mechanism of wheat bran arabinoxylan on the freeze-thaw stability of gluten protein: From the perspectives of spatial conformation and molecular polymerization of gluten protein and micro-morphology of gluten network - Mengyuan Li; Lingfang Zhang; Yuwen Wang; Xichen Lin; Xinhao Li; Li Li; Sen Ma (Food Hydrocolloids, 2026)

Hollow Li/Al-LDH architecture engineering to accelerate mass transfer for high-efficiency low-grade lithium extraction - Chenghao Qiu; Yujiao Cao; Haiping Su; Jun Chen; Jianguo Yu; Sen Lin (Desalination, 2026)

New perspectives on the role of oil-gas in mineralization of sandstone-hosted uranium deposits: Carbonate evidence from Yuejin Ⅱ, Qaidam Basin, China - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Jun-Ying Ding; Zhi-Lin Cheng; Zhao-Hui Li; Xue-Feng Gao; Ping Feng (Journal of Asian Earth Sciences, 2026)

Insights from stratigraphic reconfiguration induced by the South Pole-Aitken massive impact - Sheng Gou; Zongyu Yue; Yangting Lin; Bin Su; Zhanchuan Cai; Roberto Bugiolacchi; Kaichang Di; Patrick C. Pinet; Yuyang He; Honglei Lin; Hengci Tian; Sen Hu; et al. (Icarus, 2026)

Lunar transient atmosphere recorded in Chang'e 6 impact glass beads - Ziyan Han; Hejiu Hui; Sen Hu; Zhiyong Xiao; Fanglu Luo; Di Zhang; Yutao Lin; Huicun He; Liang Gao; Yue Zhang; Wenxin Ouyang; Yu Li; et al. (Earth and Planetary Science Letters, 2026)

Efficient lithium recovery and valorization from high‑sodium industrial wastewater - Yujiao Cao; Chenghao Qiu; Zhiheng Chen; Jun Chen; Jianguo Yu; Sen Lin (Chemical Engineering Journal, 2026)

Chalcopyrite as an indicator of uranium mineralization in the Qigequan deposit, western Qaidam Basin: Constraints from mineralogy, geochemistry, and sulfur isotopes - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Jun-Ying Ding; Wen-Yi Wu; Chen Zhang; Zhe Chi; Zhi-Lin Cheng; Bin Guo; Yi-Fan Gao (Journal of Geochemical Exploration, 2026)

Mechanisms governing responses of agriculturally important insects to global change - Chun-Sen Ma; Gang Ma; Qing-Cai Lin (Current Opinion in Insect Science, 2026)

Atomic-scale matrix partitioning of polar and antipolar motifs for high-density energy storage capacitors - Dingheng Lin; Bin Kong; Jinjun Liu; Jiarong Lv; Ya Yang; Wei Zhang; Sen Chen; Ning Liu; Zhongbin Pan (Chemical Engineering Journal, 2026)

Multi-level optimized displacement field reconstruction in icebreaker structures using inverse finite element method - Sen Wan; Meng Zhang; Lin Ren; Zhaochun Zhang; Donghui Wang; Ding Chen; Xiaohui Zhang; Haibo Hu; Nan Li (Ocean Engineering, 2026)

Stabilization of dispersive soil by iron ore tailings: A sustainable solution combining waste valorization and geotechnical enhancement - Yuhui Wu; Xiaoqing Yuan; Huicheng Fu; Sen Lin; Xin Xu; Yuxuan Zhou; Xiaoqiang Wang (Minerals Engineering, 2026)

Impact origin of pink spinel in the Chang’e-6 lunar soils - Linxi Li; Guangyuan Yu; Sen Hu; Hejiu Hui; Yi Chen; Qiu-Li Li; Wei Yang; Lihui Jia; Di Zhang; Shitou Wu; Guoqiang Tang; Hao Wang; et al. (Geochimica et Cosmochimica Acta, 2026)

Hydraulic kinetic energy-powered microbial piezo-synthesis of formate from carbon dioxide - Yao Li; Tuoyu Lin; Meiwei Guo; Liying Zhang; Sen Qiao (Chemical Engineering Journal, 2026)

Arbuscular mycorrhizal symbiosis decouples arsenic risk from saponin biosynthesis in Panax notoginseng (Araliaceae) by reprogramming rhizosphere and root processes - Xing-Kai Zhang; Xian-Nv Long; Shu-Shuang Tang; Tai-Xiong Zheng; Di Chen; Fu-Gang Wei; Yan-Lin Wang; Yue Wu; Kai Dai; Guan-Hua Cao; Sen He (Journal of Hazardous Materials, 2026)

Soil quality degradation induces synergistic evolution of carbon components: Microbial extracellular polymeric substances - driven mechanism - Renjie Hou; Sisi Liu; Anshuang Su; Miao Wang; Hai Wang; Sen Lin; Xin Zhao; Xu Leng; Jian Zhang; Lan Luo; Chunjiao Wang (Journal of Environmental Management, 2026)

Sedimentation rate changes revealing the evolution of circum–Arctic ice sheets since the Last Interglacial - Song Zhao; Dong Wu; Yu-Ying Zhang; Chao Cui; Sen Shan; Peng Ren; Lin-Sen Dong; Wei-Bin Zhang; Shu-Wei Sun; Yan-Guang Liu (Global and Planetary Change, 2026)

Nine previously undescribed immunosuppressive ent-labdane diterpenoids from the roots of Eurysolen gracilis - Lin-Lin Teng; Yan-Chun Liu; Chao-Jiang Xiao; Shu-Xi Jing; De-Sen Li; Ran Xu; Xiao-Nian Li; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Mean warming enhances insect resilience to high temperatures: species-specific evidence from two wheat aphids - Xue-Jing Wang; Yu Wang; Shu-Lin Ning; Jia-Qi Li; Biao Cui; Long-Fei Yue; Li-Yan Wang; Chun-Sen Ma (Journal of Insect Physiology, 2026)

Application of short-wave infrared spectroscopy in sandstone-type uranium deposits: A case study of the Yuejin-II uranium deposit in the Qaidam Basin, China - Wen-Yi Wu; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Yi-Han Lin; Yan Zhou; Chen Zhang; Ruo-Yu Shi; Xue-Feng Gao; Duo Wang; Bin Guo; Xiao-Qin Xu; et al. (Journal of Geochemical Exploration, 2026)

Microbially induced mineralization for mine tailings treatment: Progress, challenges, and future prospects - Zhimin Li; Xiaoqing Yuan; Huicheng Fu; Sen Lin; Xin Xu (Journal of Environmental Management, 2026)

Development and validation of a new derivatization-based quantitative analysis of multi-components by single marker strategy for simultaneous quantification of biogenic amines in fermented wine - Yue-Cai Hou; Xiao-Feng Huang; Ying Xue; Zhi-Xiang Yang; Lin-Sen Qing (Food Research International, 2026)

Topology optimization of NURBS-based composite shells with an integrated bidirectional parametric physical co-design strategy - Yaya Zhang; Jichao Yin; Sen Lin; Hu Wang; Guangyao Li; Mengzhu Yang (Engineering Structures, 2026)

NphosNet: Predicting Protein N-Phosphorylation Sites via xLSTM and Enhanced PLM Features with a Weighted Three-Channel Cross-Attention Mechanism - Lun Zhu; Yiyu Lin; Sen Yang (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Precise perception of surface tackiness enabled by a soft single-sensing-element tactile sensor - Ying Yang; Mingwei Gu; Jia-Sen Xie; Xingyu Ma; Yan-Na Lu; Lin Zheng; Jinhui Gu; Junshuai Chen; Yunjie Lu; Denys Makarov; Jin Ge (Science Bulletin, 2026)

Diurnal temperature fluctuations drive compartment-specific microbial dynamics in tissue and skeleton of Stylophora pistillata from marginal reefs - Jia-Min Kao; Chih-Ying Lu; Sen-Lin Tang; Shinya Shikina; Sung-Yin Yang; Shan-Hua Yang (Marine Environmental Research, 2026)

Association between lipid oxidation, water activity and aflatoxin B1 risk reversal in stored sunflower seeds: A storage microenvironment observation study - Sen Zeng; Jiamin Song; Xuan Ou; Tinyan Sang; Siying Lin; Ruixia Zhang; Jie Chen; Yuhua Tang; Songlei Wang; Yanan Sun (Journal of Stored Products Research, 2026)

Climate change and pesticide resistance: a synthesis on emerging mechanisms and evolutionary dynamics - Chun-Sen Ma; De-Xian Li; Jin-Chen Wei; Qing-Cai Lin (Current Opinion in Insect Science, 2026)

Antimicrobial and Antitumor Activities of Endophytic Fungi from the Medicinal Plant Paris polyphylla var. yunnanensis - Jing Zhang; Hao-Lin Yu; Yu Zhang; Chen-Sen Xu; Chao Wang; Yi-Lin Liu; Yi-Bo Shen; Jin-Zhong Hu; Zhi-Xin Liao (Current Microbiology, 2026)

Ejecta from Chaffee S Crater in Chang’E-6 Landing Site Constrained by Seifertite-Bearing Norite - Zhan Zhou; Sen Hu; Yubing Gao; Linxi Li; Huicun He; Liang Gao; Mengfan Qiu; Lixin Gu; Xu Tang; Xiaoguang Li; Wei Yang; Yangting Lin; et al. (Journal of Earth Science, 2026)

Evaluation of different types of isotope-labelled steroids based on liquid chromatography–mass spectrometry - Yameng Zhao; Luqi Sun; Pengshuai Zhang; Sen Xu; Shenghao Zhu; Lantao Zhang; Mingyang Hu; Jinglan Yu; Zhaocong Shang; Lin Zou; Wen Lei (Isotopes in Environmental and Health Studies, 2026)

Chang’e-6 lander reveals local hour-scale temporal variations in lunar surface water - Honglei Lin; Heng-Ci Tian; Sheng Gou; Wei Yang; Jinning Li; Li Liu; Kai Fan; Sen Hu; Rui Xu; Zhiping He; Yong Wei; Yangting Lin (Science Bulletin, 2026)

Anti-leukemia steroidal saponins from Paris polyphylla var. yunnanensis - Yu Zhang; Yu-Chen Zhang; Yu-Chen Fan; Chen-Sen Xu; Hao-Lin Yu; Chao Wang; Jing Zhang; Yi-Lin Liu; Yi-Bo Shen; Chao Liu; Jin-Yue Sun; Jin-Zhong Hu; et al. (Phytochemistry, 2026)

Biodegradation of tetracycline antibiotics: Advances and insights into microbial resources, enzymatic mechanisms, and remediation potential - Aojie Lei; Mengyao Wang; Yaxin Pei; Qipeng Cheng; Hongyuhang Ni; Sen Yang; Hui Lin; Xinyu Liu; Hongge Chen (Journal of Hazardous Materials, 2026)

Nanofiber engineering of covalent organic frameworks via monomer–solvent synergy for high-efficiency uranium capture - Xiao-yi Tang; Qun-yan Wu; Yi-chen Huang; Peng-fei An; Lin Wang; Ji-pan Yu; Shu-sen Chen; Zi-jie Li; Li-yong Yuan; Wang-suo Wu; Zhi-fang Chai; Wei-qun Shi (Journal of Hazardous Materials, 2026)

Duration of high temperature-pressure conditions in impact-induced plumes on the Moon - Xiaoying Liu; Chi Zhang; Zongyu Yue; Lixin Gu; Jing Li; Heng-Ci Tian; Sen Hu; Yangting Lin (Icarus, 2026)

Interleukin-12 Supports Self-renewal Division of Mouse Hematopoietic Stem Cells in Polyvinyl Alcohol-Based Culture - Jinglei Zhai; Xialin Li; Meiling Yin; Sen Zhang; Xiaoming Liu; Lisha Wang; Nini Wang; Lin Wang; Hideo Ema; Fang Dong (Stem Cell Reviews and Reports, 2026)

Deciphering multi-stage W-Sn mineralization at ore-field scale: new U-Pb geochronology and trace element fingerprinting from the world-class Dayu district, Nanling - Kai-Han Zhang; Pei Ni; Jun-Yi Pan; Yao-Hui Jiang; Guo-Guang Wang; Ming-Sen Fan; Gen-Wen He; Lin-Lin Peng; Zhe Chi; Liang Han; Jun-Ying Ding; Wen-Sheng Li (International Geology Review, 2026)

A hybrid spatial framework for risk mapping and driving factor diagnosis of soil combined contamination in Guangzhou - Lian Chen; Zhenjiang Wang; Lingyun Sun; Zhipeng Wu; Sen Lin; Dan Wang; Jianan Wu; Zhiyi Li; Gaocong Li (Journal of Geochemical Exploration, 2026)

Ti3C2 MXene-Based composites for photocatalytic antibiotic degradation: Etching strategies, mechanistic insights, and future perspectives - Zeng Liu; Siao Zhang; Yanling Guan; Sen Wang; Chunpeng Leng; Yue Yuan; Lin Liu; Guozhu Bo; Yong Yang; Fuping Li; Hao Wang (Journal of Environmental Management, 2026)

4-hydroxybenzoic acid-assisted formic acid preserves lignin structure during efficient hemicellulose removal in bamboo biorefinery - Weidong Li; Hanwen Ge; Sen Ma; Lei Liu; Lin Luo; Zihao Qin; Aiyong He; Chao Wang; Xianhai Zeng (Chemical Engineering Journal, 2026)

Sn2+ doping-induced activation of inert adsorption sites in Li/Al-LDHs for selective lithium extraction from brines - Rui Zhang; Chenlu Yan; Jun Chen; Ting Wei; Jianguo Yu; Sen Lin (Chemical Engineering Journal, 2026)

Oyster-derived Zinc Exhibits Superior Anti-anemic Efficacy and Bioavailability Compared with Conventional Zinc Supplements - Yen-Hua Chen; Hui-Lin Feng; Jia-Ling Tang; Chen-Wei Chang; Sen-Shyong Jeng (Biological Trace Element Research, 2026)

Characterization of leak flow from pipes under the effect of cavitation in water distribution systems - Yuanzhe Li; Jinliang Gao; Jianxun Chen; Kunyi Li; Shihua Qi; Sen Lin (Water Research, 2026)

Durability analysis of using MICP to address dispersive soil issues in seasonal freezing areas - Xiaoqing Yuan; Yuhui Wu; Cencen Niu; Xiaolong Yang; Sen Lin; Zeju Wu; Qing Wang; Hui’e Chen; Xin Xu; Hua Du (Soil and Tillage Research, 2026)

A novel mechanism of uranium mineralization: The role of zircon adsorption at the Qigequan deposit, Qaidam Basin, NW China - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Zhe Chi; Zhi-Lin Cheng; Wen-Yi Wu; Chen Zhang; Bing-De Qi; Xue-Bin Wei (Sedimentary Geology, 2026)

Neonicotinoids disrupt flight, bioenergetic homeostasis and neurotransmission in honey bees - Zepu Gao; Lin Ji; Wennan Luo; Zibo Feng; Xuebing Leng; Yongqiang Ma; Yaoguang Wei; Sen Pang; Dong An; Huizhe Lu (Journal of Hazardous Materials, 2026)

Wolframite and cassiterite geochemistry deciphers W–Sn ore formation: A case study from the Zuoba quartz-vein tungsten deposit, South China - Kai-Han Zhang; Jun-Yi Pan; Pei Ni; Gen-Wen He; Lin-Lin Peng; Ming-Sen Fan; Yuan-Long Zhang; Wen-Sheng Li (Journal of Asian Earth Sciences, 2026)

Bioactive plant compounds and exercise: from molecular mechanisms to clinical applications - Sen Lin; Jiayu Jiang; Jingjing Ren; Mohammad J. Rezaei (Phytochemistry Reviews, 2026)

Multi-source remote sensing for spatial mapping of salt-affected agricultural soils in Taiwan - Nguyen-Thanh Son; Chein-Hui Syu; Chi-Farn Chen; Cheng-Ru Chen; Huan-Sheng Lin; Yi-Ting Zhang; Tsang-Sen Liu; Chun-Chien Yen (Applied Geomatics, 2026)

An efficient strategy to separate nanoplastics from water using anisotropic magnetic Janus particles - Ruiqi Yan; Sen Lin; Xia Yu; Lei Zhang; Jiaxi Wang; Wentao Zhao; Mingyang Xing; Qian Sui (Water Research, 2026)

Co-pyrolysis-to-co-gasification continuum of Pennisetum hydridum and waste tires: Temperature/atmosphere/synergy characterization of tar/char/gas products - Sen Lin; Xin Chen; Guopeng Ke; Jingyong Liu; Zhibin Chen; Leyao Tao; Weijie Li; Fatih Evrendilek; Sheng Zhong; Zuoyi Yang; Yao He; Liangzhong Li (Journal of Cleaner Production, 2026)

Beyond the native state: Revolutionizing food phenolic acids profiling through advanced chemical derivatization and sample pretreatment (2003–2025) - Xiao-Feng Huang; Ying Xue; Yue-Cai Hou; Lin-Sen Qing (Food Research International, 2026)

Dual-phase anion engineering for boosting lithium capture by Li/Al-LDHs - Yujiao Cao; Chenghao Qiu; Jipeng Li; Jun Chen; Jianguo Yu; Sen Lin (Desalination, 2026)

Defect passivation with Pb for high-performance Sb2S3 solar cells via vapor transport deposition - Gan Huang; Xin-Yi Cai; Hu Li; Jin-Rui Cai; Ying-Sen Xia; Zhi-Ping Huang; Li-Mei Lin; Fu-Bao Gong; Shui-Yuan Chen; Gui-Lin Chen (Chemical Engineering Journal, 2026)

Optical properties of dissolved organic matter play pivotal roles in mediating trace metal forms in a mangrove-dominated tidal estuary - Keisuke Nakayama; Meng-Chi Hung; Chih-Yu Chiu; Sen-Lin Tang; Mei-Li Hsueh; Chin-Ching Wu; I-Hao Hung; Ya-Hsin Liu; Jeng-Wei Tsai (Marine Pollution Bulletin, 2026)

Enhanced norfloxacin oxidation with an Fe(VI)/peroxydisulfate-quinone process: iron species-driven multi-oxidation, quinone-based regulation, and density functional theory analysis - Xiao Luo; Yihan Li; Xiaoke Ma; Tapas Sen; Lin Zhao; Yongkui Yang; Peizhe Sun (Water Research, 2026)

Delivery of carbonaceous materials to the Moon - Linxi Li; Mengfan Qiu; Sen Hu; Hejiu Hui; Yi Chen; Qiu-Li Li; Wei Yang; Yuyang He; Shitou Wu; Hao Wang; Guoqiang Tang; Di Zhang; et al. (Icarus, 2026)

Quadratic polynomial prediction model-based isotope-coded equivalent reporter ion assay: A novel single-calibration LC–MS/MS strategy for sensitive quantification of steroidal sapogenin isomers in functional foods - Yue-Cai Hou; Chu Chen; Xiao-Feng Huang; Lin-Sen Qing (Food Chemistry, 2026)

Metabolic model-guided strain design for improved succinic acid production in Yarrowia lipolytica - Wentao Tang; Sen Lin; Guanghao Chen; Tianwei Hao (Bioresource Technology, 2026)

A Novel Algorithm for Optimizing Structure of In-Situ Supplementary Irrigation Device for Afforestation in Dryland - Bokun Jia; Sen Zhai; Lin Zhang; Lijie Liu; Yong Yang; Xufei Liu; Shoujun Wu; Xin Hui (Water Resources Management, 2026)

Alterations in Gut Microbiota and their Association with Colonic Permeability and Inflammation in LPS-induced Sepsis Mice - Mengke Zhang; Yanyan Shu; Jingnan Yang; Sen Sang; Xiaoming Liu; Yuxia Li; Changjiang Qin; Lei An; Xuhong Lin (Current Microbiology, 2026)

First report of Thraustochytrium caudivorum isolated from the undulated surf clam (Paratapes undulatus): Morphological, molecular, and ecological insights under climate change - Yu Chen; Seung-Hyeon Kim; Jinxia Long; S.D.N.K. Bathige; Hyoun Joong Kim; Sen-Lin Tang; Kyung-Il Park (Protist, 2025)

Photocatalytic of hydrogen peroxide production on chelating agent decorated zinc cadmium sulfide@halloysite hybrid - Sen Lin; Shiyong Sun; Jun Liu; Xiang Li; Haoming Tang; Lin Gong; Xingyun Yang (Journal of Environmental Chemical Engineering, 2025)

Chromosome-level genome assembly reveals divergent immune mechanisms in the genus Meretrix - Che-Chun Chen; Te-Hua Hsu; Hsin-Yun Lu; Sen-Lin Tang; Ying-Ning Ho (Fish & Shellfish Immunology, 2025)

A new 2-arylbenzofuran derivative and other constituents from Smilax china L. and their chemotaxonomic significance - Li-Juan Hu; Xian-Sheng Ye; Kuan Lin; Jie Gao; De-Sen Yang; Guo-Ping Gan; Xi-Ji Shu; Wei Liu; You-Hua Yang (Biochemical Systematics and Ecology, 2025)

Mechanism and Treatment Effect of Antibiotic Resistance Genes in Wastewater During Constructed Wetland Operation - Zeng Liu; Siao Zhang; Yanling Guan; Sen Wang; Xi He; Chunpeng Leng; Yunlong Zhou; Yue Yuan; Lin Liu; Fuping Li; Hao Wang (Water Conservation Science and Engineering, 2025)

Bacterial community formation on plastic and glass in coral reefs - Yusuke Iwaki; Kohei Hamamoto; Fabian Gösser; Chengze Li; Jeffrey Jolly; Sen-Lin Tang; Timothy Ravasi; James Davis Reimer (Coral Reefs, 2025)

Induced bleaching enhances cold tolerance in coral larvae: a potential strategy for cryopreservation optimization - Federica Buttari; Arah Narida; Sujune Tsai; Cheng-Liang Huang; Zhi-Hong Wen; Sen-Lin Tang; Chiahsin Lin (Coral Reefs, 2025)

Dynamics of multiple rogue waves for (3+1)-dimensional variable-coefficient potential Yu-Toda-Sasa-Fukuyama equation - Yi-Lin Tian; Wen-Yuan Li; Nong-Sen Li; Rui-Gang Zhang; Ji-Feng Cui (Wave Motion, 2025)

Layer-by-layer assembly mechanism of particulate-continuous phase for sandwich-like nanoparticles in oral colon-targeted protein delivery - Wen-Xuan Hu; Chang-Sen Jin; Si-Lin Li; Jia-Yang Fu; Liang-Sen Liao; Xiuzhu Yu; Shuang-kui Du (Food Chemistry, 2025)

Consumption of fermented Cd and Pb contaminated wheat flour increases potential health risk - Weiqin Xing; Zhexu Si; James A. Ippolito; Guobing Lin; Farzana Kastury; Sen Ma; Kunyan Qiu; Linlin Zhao; Lena Q. Ma; Liping Li (Food and Chemical Toxicology, 2025)

Granulating-avoiding aluminum-based adsorbents for fast salt lake lithium extraction with low freshwater consumption - Yujiao Cao; Jun Chen; Sen Lin; Jianguo Yu (Chemical Engineering Journal, 2025)

Efficacy of a non-recombinant NADC34-like PRRSV-2 vaccine candidate against a recombinant NADC34-like PRRSV-2 isolate - Ming Qiu; Shuai Li; Meng Cui; Shuai Yang; Xiaoyang Zhu; Yifan Meng; Yanhan Lin; Hong Lin; Zhe Sun; Yuan Wang; Sen Jiang; Wanglong Zheng; et al. (Veterinary Microbiology, 2025)

Ribociclib derivative Rib-CA suppresses breast cancer progression via p53-dependent apoptosis - Mengwei Song; Ying Zhou; Xudong Yu; Boyu Zhang; Sen Wang; Kadirya Asan; Zihao Yang; Haiyan Lin; Jian Wang; Xiaoxue Song; Yongyuan Jiang; Si Chen; et al. (Toxicology and Applied Pharmacology, 2025)

Synthesis of novel thiol-functionalized halloysite nanotube/ organophyllosilicate composite for efficient removal of aqueous U(VI) - Edward Opong Acheampong; Ke Wang; Haoming Tang; Sen Lin; Shiyong Sun (Journal of Environmental Chemical Engineering, 2025)

Microstructure-property relationships in Cu/N-TiO₂ photocatalytic concrete for marine applications: Role of preparation strategies - Guoliang Lin; Mengchen Huang; Sen Chen; Kun Li; Kun Han; Minyi Liu; Yuxiang Li; Wenhua Chen (Journal of Environmental Chemical Engineering, 2025)

Detoxifying zinc oxide nanoparticles during sludge anaerobic digestion in the presence of polyferric sulfate - Yongkui Yang; Junxiang Huang; Sen Qu; Guangxue Wu; Yiwen Liu; Yifeng Ling; Peizhe Sun; Yingxin Zhao; Lin Zhao (Journal of Environmental Chemical Engineering, 2025)

Corrigendum to “Engineered zwitterionic hydrogel with extreme environment resilience: High ionic conductivity, subzero tolerance, and potential for multimodal sensing and optical applications across devices” [Chem. Eng. J. 510 (2025) 161390/CEJ 161390] - Yan-Na Lu; Kai Mo; Mingwei Gu; Jia-Sen Xie; Ying Yang; Lin Zheng; Xiang-Ru Liu; Yunjie Lu; Jun-Shuai Chen; Jin Ge (Chemical Engineering Journal, 2025)

Senegenin ameliorates diabetic encephalopathy via promoting mitophagy and repressing NLRP3 inflammasome activation - Xiao-dan Yan; Yu Yang; Wan-ting Zhang; Qing-quan Kong; Xi-tong Zheng; Lin-sen Li; Qing Yu (Psychopharmacology, 2025)

Effect of Spatial Variability in the Geometry of Fractures on Granite Slope Stability - Lin Jia; Jing-Sen Cai; Li Wu; Tian-Chyi Jim Yeh; E-Chuan Yan; Yi Du (Journal of Earth Science, 2025)

Unveiling Unusual Ecofunctional Traits of Endozoicomonas Species Through Comprehensive Comparative Genomics - Sim Lin Lim; Ching‐Hsiang Chin; Yu‐Jing Chiou; Ming‐Tsung Hsu; Pei‐Wen Chiang; Hsing‐Ju Chen; Yung‐Chi Tu; Wen‐Shyong Tzou; Sen‐Lin Tang (Environmental Microbiology, 2025)
Endozoicomonas is an omnipresent marine bacterial genus, associated with various marine organisms, that contributes to host health, nutrient cycling and disease resistance. Nonetheless, its genomic features remain poorly characterised due to a paucity of high‐quality genomes. In this study, we sequenced 5 novel Endozoicomonas strains and re‐sequenced 1 known strain to improve genomic resolution. By integrating these 6 high‐quality genomes with 31 qualified published genomes, our pan‐genomic analysis revealed variation in genetic traits among clades. Notably, Endozoicomonas lacks quorum‐sensing capabilities, suggesting resistance to quorum quenching mechanisms. It also lacks the capacity to synthesise and transport vitamin B12, indicating that it does not supply this nutrient to holobionts. Remarkably, Endozoicomonas genomes encode 92 identified giant proteins (15–65 kbp). These proteins cluster into three major groups associated with antimicrobial peptide synthesis, exotoxin production and cell adhesion. Additionally, we found that Endozoicomonas has acquired prophages from diverse sources via infection or other types of gene transfer. Notably, CRISPR‐Cas sequences suggest evolutionary trajectories independent of both prophage acquisition and phylogenetic lineage, implying potential geographic influences or environmental pressures. This study provides new insights into the genomic diversity of Endozoicomonas and its genetic adaptations to diverse hosts.

A grid search-based optimal trajectory planning approach for automatic berthing of underactuated unmanned surface vehicles - Shidi Wu; Shifeng Ding; Lin Geng; Zihan Chen; Sen Han; Li Zhou (Ocean Engineering, 2025)

Geochemistry of sulfides from massive carbonate replacement type tin ore at Gaofeng, Dachang orefield: Insights into precipitation conditions and enrichment of critical metals - Yu-Pei Liu; Pei Ni; Jun-Yi Pan; Wen-Chao Su; Stefano Albanese; Jian-Ming Cui; Yuan-Feng Cai; Ming-Sen Fan; Zhi-Lin Cheng (Journal of Geochemical Exploration, 2025)

Comparative Analysis of Stent-Assisted Versus Non-Stent-Assisted Coiling in the Management of Ruptured Intracranial Aneurysms: A Systematic Review and Meta-Analysis - Yu-Hu Ma; Yong-Lin He; Xiao-Yue Zhang; Rui Shang; Hai-Tao Hu; Ting Wang; Sen Lin; Ya-Wen Pan; Chang-Wei Zhang (Translational Stroke Research, 2025)

Stability of cement-red soil ecological substrate slope under simulated rainfall conditions: experiment and finite element analysis - Guoliang Lin; Sen Chen; Pengpeng Jiang; Mengchen Huang; Xiaoyi Zhang; Wanxi Jiang; Aoxiang Lin; Minyi Liu (Bulletin of Engineering Geology and the Environment, 2025)

Antitumor activity and mechanistic study of steroidal saponins from the rhizomes of Paris polyphylla var. yunnanensis - Yu Zhang; Yu-Chen Fan; Yu-Chen Zhang; Qing Li; Yun-Yun Su; Chen-Sen Xu; Hao-Lin Yu; Chao Wang; Jing Zhang; Zhi-Xin Liao (Phytochemistry, 2025)

Cycleift: A deep transfer learning model based on informer with cycle fine-tuning for water quality prediction - Yang Yu; Shixin Zhao; Lintong Han; Lin Peng; Yanmei Xu; Qiujin Tian; Sen Chen; Zuogang Yang; Qiude Li; Zuquan Hu (Stochastic Environmental Research and Risk Assessment, 2025)

Systematic analysis of associations between obesity and memory decline - Ying Yue Huang; Wei Sen Zhang; Jiao Wang; Chao Qiang Jiang; Feng Zhu; Ya Li Jin; Kar Keung Cheng; Tai Hing Lam; Lin Xu (GeroScience, 2025)
Despite the development of numerous obesity indicators, the optimal measure associated with memory remains to be elucidated. We examined and compared these associations whilst also exploring potential interactions with education. We analysed the associations between 20 obesity indicators and memory (measured by Delayed Word Recall Test (DWRT)) in middle-aged and older participants from Guangzhou Biobank Cohort Study by linear regression and stratification analyses. We used two-sample Mendelian randomisation (2SMR) to analyse the associations of obesity with cognitive performance. Of 20 obesity indicators, 6 and 7 were associated with poorer memory function measured by baseline and follow-up DWRT; 7 and 10 with faster memory decline measured by mean annual change (MAC) and MAC rate of DWRT. Central obesity measured by waist-to-hip-to-height ratio (WHHR) z -score showed the greatest effect size, with the β s (95% CIs) being − 0.09 (− 0.11 to − 0.07), − 0.07 (− 0.09 to − 0.04), − 0.02 (− 0.03 to − 0.01) and − 0.49 (− 0.69 to − 0.29), respectively. The associations were weaker in those with higher education ( P for education-interaction from 0.008 to 0.049). In 2SMR, body mass index (BMI), waist circumference and BMI-adjusted waist-to-hip ratio were negatively associated with cognitive performance using inverse-variance weighted method, with β s (95% CIs) being − 0.11 (− 0.15 to − 0.07), − 0.07 (− 0.12 to − 0.02) and − 0.06 (− 0.09 to − 0.02), respectively. In conclusion, obesity, especially central obesity measured by WHHR, was associated with poorer memory function and faster memory decline in middle-aged and older people, with a weaker association observed amongst those with higher education. Graphical Abstract

Structural analysis and numerical modeling of multi-stage tectonic deformation in the Ziliujing anticline, SW Sichuan Basin, China: Implications for deformation propagation in salt-bearing fold-and-thrust belts - Jiawei Liu; Gang Rao; Sen Bai; Xiaolin Xiong; Jinwu Zhang; Wenxiong Yang; Chao Yin; Yaqi Zhong; Pengcheng Tang; Jianhua Qiu; Lin Gao (Tectonophysics, 2025)

Untargeted metabolomics and network pharmacology reveal the uric acid-lowering effects of alcohol extract of Gnaphalium affine and its extracts in hyperuricemic rats - Chen Wang; Xinchao He; Lijuan Rao; Jiajing Liao; Jin Qian; Xuefeng Yu; Sen Mei; Suqin Lin; Linqian Xu; Guiming Fu; Yin Wan (Food Bioscience, 2025)

Comparing Cr(III) oxidation intermediated by different manganese oxidizing bacteria: Efficiencies, kinetic and key structure characteristics of biogenic manganese oxides - Guangyuan Tu; Chunyu Ou; Qi Liao; Xiaoming Zhang; Shuangle Hou; Lin Yu; Kun Li; Sen Yang; Qi Li; Weichun Yang; Qingzhu Li; Mengying Si; et al. (Environmental Research, 2025)

Spatial patterns of essential fish habitats in the western Taiwan coast - Yu-Jia Lin; Chien-Cheng Lai; Hsu-Sen Chen; Tsu-Chun Chen; Kuo-Shu Chen; Norhafiz Hanafi; Pei-Jie Meng; Ying-Chin Fang; Chiee-Young Chen; Hsin-Ming Yen; Meng-Hsien Chen (Estuarine, Coastal and Shelf Science, 2025)

Localized chemical disorder induced superior energy storage performance of PbZrO3-based antiferroelectric ceramics - Mingqi Shi; Xingke Pan; Dingheng Lin; Ning Liu; Wei Zhang; Sen Chen; Peng Li; Jinjun Liu; Hongzhen Xie; Zhongbin Pan (Chemical Engineering Journal, 2025)

3D printed microtissue cassettes enabling high throughput proton radiobiological assays - Chih-Tsung Yang; I-Chun Cho; Ching-Fang Yu; Edward Cheah; Tesi Liu; Yi-Ping Lin; Sing-Yu Hu; Jyun-Wei Jheng; Ivan Kempson; Tsi-Chian Chao; Sen-Hao Lee; Eva Bezak; et al. (Analytica Chimica Acta, 2025)

Effective SSR markers for assessing population structure, genetic diversity, and volatile compounds in Atractylodis Rhizoma - Haotian Zhong; Lina Chen; Lei Chen; Xiao Huang; Ling Gong; Juan Hu; Yuling Zeng; Kun Yu; Lin Sen (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Targeted and non-targeted metabolic analysis of chlorpromazine in grass carp as well as the in-silico and metabolomics toxicity assessment - Jinxia Dai; Sen Zhang; Hui Lin; Jun-qin Qiao; Hong-zhen Lian; Chun-xiang Xu (Journal of Hazardous Materials, 2025)

Corrigendum to “Discovery of a highly shocked alkali suite clast in the Chang'e-5 lunar soils” [Icarus 429 (2025) 116448] - Mengfan Qiu; Sen Hu; Huicun He; Zongyu Yue; Hejiu Hui; Jialong Hao; Ruiying Li; Sheng Gou; Lixin Gu; Xu Tang; Jinhua Li; Wei Yang; et al. (Icarus, 2025)

Thin basaltic regolith at the Chang'e-6 landing site - Sheng Gou; Zongyu Yue; Yangting Lin; Kaichang Di; Patrick C. Pinet; Wei Yang; Yuyang He; Yi Chen; Roberto Bugiolacchi; Hengci Tian; Honglei Lin; Sen Hu (Earth and Planetary Science Letters, 2025)

Engineered zwitterionic hydrogel with extreme environment resilience: High ionic conductivity, subzero tolerance, and potential for multimodal sensing and optical applications across devices - Yan-Na Lu; Kai Mo; Mingwei Gu; Jia-Sen Xie; Ying Yang; Lin Zheng; Xiang-Ru Liu; Yunjie Lu; Jun-Shuai Chen; Jin Ge (Chemical Engineering Journal, 2025)

1DCNN-based prediction methods for subsequent settlement of subgrade with limited monitoring data - Sen-Lin Xie; Anfeng Hu; Meihui Wang; Zhi-Rong Xiao; Tang Li; Chi Wang (European Journal of Environmental and Civil Engineering, 2025)

Discovery of a highly shocked alkali suite clast in the Chang'e-5 lunar soils - Mengfan Qiu; Sen Hu; Huicun He; Zongyu Yue; Hejiu Hui; Jialong Hao; Ruiying Li; Sheng Gou; Lixin Gu; Xu Tang; Jinhua Li; Wei Yang; et al. (Icarus, 2025)

α-asarone activates mitophagy to relieve diabetic encephalopathy via inhibiting apoptosis and oxidative stress - Xiao-dan Yan; Rong-hua Fan; Yu Wang; Xiao-xu Duan; Xuan Wei; Lin-sen Li; Qing Yu (Metabolic Brain Disease, 2025)

Synergistic atmospheric influence on the co-pyrolysis of antibiotic sludge and waste bicycle tires: Optimal drivers, products, and pathways - Dajie Jia; Tao Chen; Liangzhon Li; Jingyong Liu; Zhibin Chen; Sen Lin; Guopeng Ke; Fatih Evrendilek; Wuming Xie; Wenxiao Huang; Chenyu Yang (Journal of Hazardous Materials, 2025)

Identification of forest priority conservation and restoration areas for different SSPs-RCPs scenarios - Miaomiao Liu; Shuang Liu; Raohan Tang; Minggao Liu; Xisheng Hu; Sen Lin; Zhilong Wu (Journal of Environmental Management, 2025)

A real-time controllable pressure-driven smart window with Cu2+ solution - Chunxiao Zhang; Dongdong Li; Lin Wang; Sen Zhang; Chao Shen; Rong Gao (Energy and Buildings, 2025)

Atmosphere-dependent pyrolytic transformability of glass fiber/epoxy resin composites in waste wind turbine blades - Siqi Chen; Jingyong Liu; Ziting Lin; Sen Lin; Liangzhong Li; Yan Chen; Fatih Evrendilek; Weixin Li; Wenxiao Huang; Chenyu Yang; Haoran Yuan; Yao He; et al. (Chemical Engineering Journal, 2025)

Constructing mullite-based catalyst by surface oxygen vacancy regulation for propane oxidation at reduced temperature - Sen Fu; Yao Nian; Changqing He; Cong Zhang; Lin He; Yong Wang; Shinee Lou; Hong Sui (Chemical Engineering Journal, 2025)

Resveratrol loaded microglia-derived exosomes attenuate astrogliasis by restoring mitochondrial function to reduce spinal cord injury - Jingwen Cui; Sen Lin; Mingyuan Zhang (Chemico-Biological Interactions, 2025)

Depositional record of metal(loid)s since late quaternary in the Laizhou Bay, China - Longlong Liu; Junfeng Gao; Shengjiang Zhang; Sen Lin; Dongdong Lu; Jialin Zhang; Xiang Xie; Bin Chen; Jiandong Qiu (Frontiers in Marine Science, 2025)
The contamination of marine ecosystems with metal(loid)s is an increasing environmental concern, largely driven by anthropogenic activities, and poses a significant risk to the health of ecosystems and human well-being. Geochemical background values represent the typical concentrations of trace elements observed in the natural environment. The utilization of disparate background values gives rise to disparate evaluation outcomes. The objective of this study was to investigate the concentration profiles of metal(loid)s (Cu, Pb, Zn, Cr, Cd, As, and Hg) along a sediment core in order to obtain background values and assess the depositional processes and contamination levels in Laizhou Bay. With the exception of arsenic, the distribution patterns of the remaining metal(loid)s were similar and could be divided into four stages, which were primarily influenced by the mean grain size and sediment sources. The results of the analysis of multiple indicators indicated that there was no evidence of heavy metal enrichment or contamination in the core sediments. Furthermore, the data demonstrated that all metal(loid)s present were of natural origin. The historical changes in metal(loid)s in the core sediments were predominantly linked to the sedimentary environment, sediment sources, and mean grain size. The mean values of the metal(loid)s in the DU 4-2 unit, formed during the Early Holocene, may be regarded as reference values for background concentrations.

A sustainable process for Pb, Zn, and Fe from copper slag by salt roasting-magnetization roasting-magnetic separation - Xinze Gao; Yinhe Lin; Dong Guan; Zhaohua Liu; Bo Deng; Qingshan Du; Yanjun Liu; Sen Yu; Juncheng Li; Lingling Cao (Process Safety and Environmental Protection, 2025)

A spatial source-oriented and probability-based risk-assessment framework for heavy metal and PAH contamination of urban soils in Guangzhou, China - Lian Chen; Minghe Xie; Gaocong Li; Sen Lin; Dan Wang; Zhiyi Li; Yuan Wang; Zhenjiang Wang (Journal of Hazardous Materials, 2025)

Dissolved oxygen activated by single-atom-state iron coupled with sodium dithionite for norfloxacin degradation: Efficiency and mechanism - Wei Song; Sen Xu; Caixia Fu; Ruiyi Huang; Hongze Fang; Li Li; Dachao Lin; Yuning Fang; Xing Du; Zhihong Wang (Journal of Cleaner Production, 2025)

Inequality repercussions of roads on the coupling relationships between carbon supply and demand - Guanmin Liang; Miaomiao Liu; Minggao Liu; Min Wu; Xueman Zuo; Xisheng Hu; Sen Lin; Zhilong Wu (Journal of Cleaner Production, 2025)

Effect of hot-air drying processing on the volatile organic compounds and maillard precursors of Dictyophora Rubrovalvata based on GC-IMS, HPLC and LC-MS - Lingshuai Meng; Yu Nie; Qingsong Zhou; Tingting Zheng; Jianxin Song; Chao Zhang; Haijiang Chen; Dong Lin; Sen Cao; Su Xu (Food Chemistry, 2025)

Echelon extraction of valuable components from salt lake brine substrate - Xiangting Tang; Jun Chen; Ye Zhang; Jianguo Yu; Sen Lin (Desalination, 2025)

A crazy trio in Parkinson's disease: metabolism alteration, α-synuclein aggregation, and oxidative stress - Sheng Li; Yanbing Liu; Sen Lu; Jiayi Xu; Xiaokun Liu; Di Yang; Yuxuan Yang; Lin Hou; Ning Li (Molecular and Cellular Biochemistry, 2025)

Corrigendum to “Revisiting the formation of lunar anorthosites via the Rb-Sr isotope systematics” [Lithos, volume 486–487, (2024) 107780] - Qing Zhou; Heng-Ci Tian; Liyu Shan; Sen Hu; Wei Yang; Maoyong He; Lei Zhang; Yangting Lin; Xianhua Li (Lithos, 2024)

Fe2O3, Al2O3, or sludge ash-catalyzed pyrolysis of typical 3D printing waste toward tackling plastic pollution - Ziting Lin; Jingyong Liu; Liangzhong Li; Haiming Cai; Sen Lin; Fatih Evrendilek; Siqi Chen; Xin Chen; Tao Chen; Yao He (Journal of Hazardous Materials, 2024)

Predicting straw drinking ability of liquid foods by pipe-flow rheometry - Sen Hu; Chunan Sun; Wei Wei; Lin Lei; Guohua Zhao; Yun Zhou (Food Research International, 2024)

Complex basalt evolution in the Chang'e-6 landing area - Sheng Gou; Zongyu Yue; Yangting Lin; Kaichang Di; Patrick C. Pinet; Roberto Bugiolacchi; Yuyang He; Wei Yang; Honglei Lin; Hengci Tian; Sen Hu (Earth and Planetary Science Letters, 2024)

Multiple hydrothermal events at martian surface revealed by H and Cl isotope systematics of melt inclusions and hydrous minerals from chassignite NWA 2737 - Sen Hu; Mahesh Anand; Ian A. Franchi; Xuchao Zhao; Alice Stephant; Magali Bonifacie; Huicun He; Wei Yang; Jialong Hao; Yangting Lin (Earth and Planetary Science Letters, 2024)

Interfacial Mo-N bonding enhancement of N-doped carbon nanosheets-stabilized ultrafine MoS2 enable ultrafast and durable sodium ion half/full batteries - Dongfei Sun; Sen Lin; Shengxu Kuai; Tiantian Zhang; Lei Liu; Jingxin Zhao; Xiaozhong Zhou; Wenwen Liu; Bingang Xu (Chemical Engineering Journal, 2024)

Effects of Different Nitrogen Fertilizer Rates on Soil Magnesium Leaching in Tea Garden - Sen Wang; Wei Lin; Qi Ye; Wenzhuo Lv; Penghui Liao; Jinhui Yu; Cong Mu; LiangQuan Wu; Muhammad Atif Muneer; Yinjie Zhang; Runzhi Zhan; Aolin Wu; et al. (Journal of Soil Science and Plant Nutrition, 2024)

Synthesis of Fe-ZSM-5 zeolite from high iron-containing palygorskite with peroxidase-like catalytic performance - Fengya Ran; Meng He; Shiyong Sun; Rui Lv; Sen Lin; Ke Wang; Yevgeny Aleksandrovich Golubev; Olga Borisovna Kotova; Elena Leonidovna Kotova (Applied Clay Science, 2024)

On the FT-ICR mass spectrometry analysis of dissolved organic matter released by adsorbent during coal chemical wastewater treatment - Qi Wei; Cai Chen; Hong-Peng Ma; Tao Liu; Bing Liu; Tian-Xiang Wang; Sen Zhang; Dan-Hui Yang; Wen-Jie Lv; Hua-Lin Wang (Science of The Total Environment, 2024)

Revisiting the formation of lunar anorthosites via the Rb Sr isotope systematics - Qing Zhou; Heng-Ci Tian; Liyu Shan; Sen Hu; Wei Yang; Maoyong He; Lei Zhang; Yangting Lin; Xianhua Li (Lithos, 2024)

Underwater image restoration via attenuated incident optical model and background segmentation - Sen Lin; Yuanjie Sun; Ning Ye (Frontiers in Marine Science, 2024)
Underwater images typically exhibit low quality due to complex imaging environments, which impede the development of the Space-Air-Ground-Sea Integrated Network (SAGSIN). Existing physical models often ignore the light absorption and attenuation properties of water, making them incapable of resolving details and resulting in low contrast. To address this issue, we propose the attenuated incident optical model and combine it with a background segmentation technique for underwater image restoration. Specifically, we first utilize the features to distinguish the foreground region of the image from the background region. Subsequently, we introduce a background light layer to improve the underwater imaging model and account for the effects of non-uniform incident light. Afterward, we employ a new maximum reflection prior in the estimation of the background light layer to achieve restoration of the foreground region. Meanwhile, the contrast of the background region is enhanced by stretching the saturation and brightness components. Extensive experiments conducted on four underwater image datasets, using both classical and state-of-the-art (SOTA) algorithms, demonstrate that our method not only successfully restores textures and details but is also beneficial for processing images under non-uniform lighting conditions.

Extremely large Cl isotopic fractionation in Chang'e-5 impact glass beads - Yue Zhang; Hejiu Hui; Sen Hu; Jialong Hao; Ruiying Li; Wei Yang; Qiuli Li; Yangting Lin; Xianhua Li; Fuyuan Wu (Earth and Planetary Science Letters, 2024)

Analysis of two-dimensional consolidation behavior of soils under cyclic loading considering exacerbated tunnel leakage - Sen-Lin Xie; An-Feng Hu; Zhi-Rong Xiao; Mei-Hui Wang; Xun-Jian Hu; Gabriele Della Vecchia; Stefano Mariani (Computers and Geotechnics, 2024)

Bimetallic MIL-68(InFe) MOF nanorods for biomimetic photocatalytic N2 fixation - Cheng Liu; Mengning Chen; Yueling Chen; Qi Chen; Jionghua Wu; Sen Lin; Ling Wu; Jimmy C. Yu (Chemical Engineering Journal, 2024)

Specific adsorption of antiviral drugs on ionic liquid-modified metal–organic framework: Adsorption behavior, mechanism, and DFT analysis - Yihan Li; Lin Zhao; Daying Chen; Tapas Sen; Guining Lu; Jiashu Liu; Xiaodong Du; Peizhe Sun; Yongkui Yang (Chemical Engineering Journal, 2024)

Active longevity and aging: dissecting the impacts of physical and sedentary behaviors on longevity and age acceleration - Ting Yu Lu; Jiao Wang; Chao Qiang Jiang; Ya Li Jin; Kar Keung Cheng; Tai Hing Lam; Wei Sen Zhang; Lin Xu (GeroScience, 2024)
Background To examine the associations of physical activity (PA) and sedentary behavior (SB) with longevity and age acceleration (AA) using observational and Mendelian randomization (MR) studies, and quantify the mediating effects of lipids. Methods In Guangzhou Biobank Cohort Study (GBCS), PA and SB were assessed by the Chinese Version of the International Physical Activity Questionnaire. Longevity was defined as participants whose age at follow-up or at death was at or above the 90th age percentile. AA was defined as the residual resulting from a linear model that regressed phenotypic age against chronological age. Linear regression and Poisson regression with robust error variance were used to assess the associations of total and specific PA in different intensities, and SB with AA and longevity, yielding βs or relative risks (RRs) and 95% confidence intervals (CIs). Two-sample MR was conducted to examine the causal effects. Mediation analysis was used to assess the mediating effects of lipids. Results Of 20,924 participants aged 50 + years in GBCS, during an average follow-up of 15.0 years, compared with low PA, moderate and high PA were associated with higher likelihood of longevity (RR (95% CI): 1.56 (1.16, 2.11), 1.66 (1.24, 2.21), respectively), and also cross-sectionally associated with lower AA (β (95% CI): -1.43 (-2.41, -0.45), -2.09 (-3.06, -1.11) years, respectively). Higher levels of moderate PA (MPA) were associated with higher likelihood of longevity and lower AA, whereas vigorous PA (VPA) showed opposite effects. The association of PA with longevity observed in GBCS was mediated by low-density lipoprotein cholesterol (LDL-C) by 8.23% (95% CI: 3.58–39.61%), while the association with AA was mediated through LDL-C, triglycerides and total cholesterol by 5.13% (3.94–7.30%), 7.81% (5.98–11.17%), and 3.37% (2.59–4.80%), respectively. Additionally, in two-sample MR, SB was positively associated with AA (β (95% CI): 1.02 (0.67, 1.36) years). Conclusions PA showed protective effects on longevity and AA, with the effects being partly mediated through lipids. Conversely, SB had a detrimental impact on AA. MPA was associated with higher likelihood of longevity and reduced AA, whereas VPA showed adverse effects. Our findings reinforce the recommendation of “sit less and move more” to promote healthy longevity, and highlight the potential risks associated with VPA in the elderly.

Xanthohumol combined with chitosan-oxidized starch film as a potential new strategy for food packaging: Characterization, physicochemical and biological properties - Fan Yang; Siyuan Chang; Lin Zhao; Jing Han; Hao Li; Sen Zhang; Sheng Guo; Jinao Duan (Food Packaging and Shelf Life, 2024)

Entire co-combustion lifecycle of sewage sludge and water lettuce (Pistia stratiotes L.) and its controls over energetic and environmental benefits - Jiayu Liang; Jingyong Liu; Fatih Evrendilek; Zhibin Chen; Liangzhong Li; Sen Lin; Ziting Lin; Lei Li; Xieyuan Wu; Li Wang; Yao He (Chemical Engineering Journal, 2024)

A humidity-driven film with fast response and continuous rolling locomotion - Sen Lin; Suqian Ma; Kunzhi Chen; Yuyu Zhang; Zhaohua Lin; Yunhong Liang; Luquan Ren (Chemical Engineering Journal, 2024)

Multicenter study on clinical outcomes and poor prognostic factors in patients with Klebsiella pneumoniae bacteremia receiving cefoperazone/sulbactam treatment - Tsung-Ta Chiang; Ming-Hsien Chiang; Hung-Jen Tang; Zhi-Yuan Shi; Mao-Wang Ho; Chia-Hui Chou; Shang-Yi Lin; Po-Liang Lu; Ting-Shu Wu; Shian-Sen Shie; Jien-Wei Liu; Feng-Yee Chang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Background Infections caused by Klebsiella pneumoniae are common and result in high mortality rates. In vitro studies demonstrated the potency of cefoperazone/sulbactam (CPZ/SUL) against Klebsiella pneumoniae . However, the clinical efficacy of CPZ/SUL for the treatment of K. pneumoniae bacteremia has not been studied. Objectives This study aimed to associate the clinical outcomes of patients with bacteremia with the minimal inhibitory concentrations (MICs) of CPZ/SUL against the causative K. pneumoniae isolates. Methods This multicenter, retrospective study was conducted in Taiwan between July 2017 and April 2021. Patients with K. pneumoniae bacteremia treated with CPZ/SUL were enrolled in this study. CPZ/SUL MICs were determined using the agar dilution method. Data on the patients’ clinical outcomes and characteristics were collected and analyzed. Results In total, 201 patients were enrolled. Among the causative K. pneumoniae isolates, 180 (89.5%) were susceptible to CPZ/SUL. Most patients ( n = 156, 77.6%) had favorable outcomes. The 30-day mortality rate was 11.9% ( n = 24). Multivariate risk analyses showed that higher APACHE II score (Odds Ratio [OR], 1.14; Confidence Interval [CI], 1.07–1.21; p < 0.001), metastatic tumors (OR, 5.76; CI, 2.31–14.40; p < 0.001), and causative K. pneumoniae CPZ/SUL MICs > 16 µg/ml (OR, 4.30; CI, 1.50–12.27; p = 0.006) were independently associated with unfavorable outcomes. Conclusion Patients with K. pneumoniae bacteremia treated with CPZ/SUL at a ratio 1:1 had favorable outcomes when the CPZ/SUL MICs were ≤ 16 µg/ml. Patients with higher APACHE II scores and metastatic tumors had unfavorable outcomes.

Exendin-4, a glucagon-like peptide-1 receptor agonist, alleviates muscular dysfunction and wasting in a streptozotocin-induced diabetic mouse model compared to metformin - Ding-Cheng Chan; Yuan-Cheng Lin; Huei-Ping Tzeng; Rong-Sen Yang; Meng-Tsan Chiang; Shing-Hwa Liu (Tissue and Cell, 2024)

Valuable components recovery from wastewater and brine using electrocoagulation-based coupled process: A systematic review - Ye Zhang; Xiangting Tang; Jiayi Zhang; Yi Zhang; Ruoning Yu; Wenshuo Wang; Sen Lin; Jianguo Yu (Desalination, 2024)

Enhancing lithium extraction from low grade salt lake brines using high powder loading aluminum-based adsorbent granules - Yanan Pan; Ye Zhang; Haiping Su; Jianguo Yu; Sen Lin (Desalination, 2024)

Co-pyrolytic drivers and volatiles of 3D printing waste and textile dyeing sludge and their multi-objective optimization - Ziting Lin; Xiaoming Li; Jingfang Mou; Fatih Evrendilek; Jingyong Liu; Jiayu Liang; Sen Lin; Haiming Cai; Yao He; Guanzheng Zhuang; Chunxiao Yang (Chemical Engineering Journal, 2024)

MSC-Derived Extracellular Vesicles Alleviate NLRP3/GSDMD-Mediated Neuroinflammation in Mouse Model of Sporadic Alzheimer’s Disease - Lishan Lin; Longxin Huang; Sen Huang; Weineng Chen; Heng Huang; Li Chi; Fengjuan Su; Xiaoqing Liu; Kang Yuan; Qiuhong Jiang; Changu Li; Wanli W. Smith; et al. (Molecular Neurobiology, 2024)

EVA1A reverses lenvatinib resistance in hepatocellular carcinoma through regulating PI3K/AKT/p53 signaling axis - Xiaokun Liu; Xiao Gao; Yuling Yang; Di Yang; Qingming Guo; Lianhui Li; Shunlong Liu; Wanxin Cong; Sen Lu; Lin Hou; Bin Wang; Ning Li (Apoptosis, 2024)

In-situ electrochemical study on the effects of Fe(III) on kinetics of pyrite acidic pressure oxidation - Yu Zhang; Can Cui; Sen Lin; Heping Li; Lian Yang; Yadian Xie; Hailiang Hu; Lingyun Zhou; Huanjiang Wang; Chunyan Li (Acta Geochimica, 2024)

Return to the Moon: New perspectives on lunar exploration - Yangting Lin; Wei Yang; Hui Zhang; Hejiu Hui; Sen Hu; Long Xiao; Jianzhong Liu; Zhiyong Xiao; Zongyu Yue; Jinhai Zhang; Yang Liu; Jing Yang; et al. (Science Bulletin, 2024)

Physicochemical, thermodynamic, and kinetic controls on volatile products, bio-oils, and biochars of Lycium barbarum pyrolysis and their multi-objective optimization - Siqi Chen; Sen Lin; Shengzheng Huang; Bin Cai; Jiayu Liang; Zhibin Chen; Fatih Evrendilek; Yao He; Sheng Zhong; Zuoyi Yang; Chunxiao Yang; Jingyong Liu (Fuel, 2024)

Micro-helical Ni3Fe chain encapsulated in ultralight MXene/C aerogel to realize multi-functionality: Radar stealth, thermal insulation, fire resistance, and mechanical properties - Sen Lin; Jing Lin; Zhiqiang Xiong; Xue He; Xin Li; Chongbo Liu; Chengying Wang; Xiaojun Zeng; Xuliang Nie; Renchao Che (Chemical Engineering Journal, 2024)

Savanna Nightjars (Caprimulgus affinis stictomus) adjust calling height to gain amplitude advantage in urban environments - Shih-Hsiung Liang; Chia-Hung Jen; Lin-Lee Lee; Chao-Chieh Chen; Bao-Sen Shieh (Journal of Ornithology, 2024)

Atmosphere-dependent combustion of Ganoderma lucidum biomass toward its enhanced transformability into green energy - Hanlin Cao; Hongda Zhan; Jianying Qi; Sen Lin; Mingzhong Ren; Jiayu Liang; Fatih Evrendilek; Yao He; Jingyong Liu (Environmental Science and Pollution Research, 2024)

First discovery of impact-induced vapor deposition of native copper, FeCo alloy and digenite from Chang'e-5 lunar soil - Jing Li; Lixin Gu; Xu Tang; Xiaoying Liu; Sen Hu; Yangting Lin (Icarus, 2024)

Multiplicative effects of co-incineration of sewage sludge and wasted oyster shells in air, CO2, and steam atmospheres on P speciation and bioavailability and metal ecotoxicity - Jiayu Liang; Zhiwei Huang; Jingyong Liu; Sen Lin; Ziting Lin; Fatih Evrendilek; Wuming Xie; Guanzheng Zhuang; Yao He; Li Wang; Chunxiao Yang (Chemical Engineering Journal, 2024)

An Automatic Approach of Video-Based Landmark Detection and Movement Analysis for Assessing Symptoms of Bradykinesia in Parkinson’s Disease - Ching-Fang Chien; Chen-Sen Ouyang; Yi-Hung Chiu; Lung-Chang Lin; Rei-Cheng Yang; Yang-Pei Chang; San-Yuan Wang; Li-Min Liou (Journal of Medical and Biological Engineering, 2024)

Theory and application of a Si-based defense barrier for plants: Implications for soil-plant-atmosphere system health - Zhihao Pang; Hongyun Peng; Sen Lin; Yongchao Liang (Critical Reviews in Environmental Science and Technology, 2024)

Monitoring of chlorophyll content in local saltwort species Suaeda salsa under water and salt stress based on the PROSAIL-D model in coastal wetland - Sen Zhang; Jia Tian; Xia Lu; Qingjiu Tian; Shuang He; Yali Lin; Shan Li; Wei Zheng; Tao Wen; Xinyuan Mu; Jun Zhang; Yurong Li (Remote Sensing of Environment, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Second-generation bioenergy to decouple fossil fuel dependency and environmental deterioration: Dynamic and optimal mechanisms and gas-to-ash products of combustion of Pennisetum hydridum - Sen Lin; Li Wang; Jingyong Liu; Zebin Wei; Fatih Evrendilek; Jiayu Liang; Ziting Lin; Zuoyi Yang; Sheng Zhong (Biomass and Bioenergy, 2024)

Regulated Necrosis in Glaucoma: Focus on Ferroptosis and Pyroptosis - Duan Chen; Sen Miao; Xuemei Chen; Zhiyi Wang; Pei Lin; Ningzhi Zhang; Ning Yang (Molecular Neurobiology, 2024)

An Hsp70 promoter–based mouse for heat shock–induced gene modulation - Hangang Chen; Yangli Xie; Mei Zhang; Junlan Huang; Wanling Jiang; Ruobin Zhang; Can Li; Xiaolan Du; Hua Chen; Qiang Nie; Sen Liang; Qiaoyan Tan; et al. (Journal of Molecular Medicine, 2024)

Catalytic co-pyrolysis of coffee grounds and polyethylene: A comparison of HZSM-5 and HY - Jiawei Fu; Sen Lin; Bin Cai; Jiayu Liang; Zhibin Chen; Fatih Evrendilek; Sheng Zhong; Zuoyi Yang; Chunxiao Yang; Yao He; Shuiyu Sun; Jingyong Liu (Fuel, 2024)

Submicron spatial resolution Pb-Pb dating for the formation age of Chang'e-5 basalt - Jia-Long Hao; Wei Yang; Hui-Cun He; Di Zhang; Sen Hu; Heng-Ci Tian; Rui-Ying Li; Yang-Ting Lin (Lithos, 2024)

Research on the Drift Prediction of Marine Floating Debris: A Case Study of the South China Sea Maritime Drift Experiment - Lin Mu; Haiwen Tu; Xiongfei Geng; Fangli Qiao; Zhihui Chen; Sen Jia; Ruifei Zhu; Tianyu Zhang; Zhi Chen (Journal of Marine Science and Engineering, 2024)
Annually, hundreds of individuals tragically lose their lives at sea due to shipwrecks or aircraft accidents. For search and rescue personnel, the task of locating the debris of a downed aircraft in the vastness of the ocean presents a formidable challenge. A primary task these teams face is determining the search area, which is a critical step in the rescue operation. The movement of aircraft wreckage on the ocean surface is extremely complex, influenced by the combined effects of surface winds, waves, and currents. Establishing an appropriate drift motion prediction model is instrumental in accurately determining the search area for the wreckage. This article initially conducts maritime drift observation experiments on wreckage, and based on the results of these experiments, analyzes the drift characteristics and patterns of the debris. Subsequently, employing a wealth of observational experimental data, three types of drift prediction models for the wreckage are established using the least squares method. These models include the AP98 model, the dynamics model, and an improved model. In conclusion, the effectiveness and accuracy of the three models is evaluated and analyzed using Monte Carlo techniques. The results indicate that the probability of positive crosswind leeway (CWL) is 47.4%, while the probability of negative crosswind leeway (CWL) is 52.6%. The jibing frequency is 7.7% per hour, and the maximum leeway divergence angle observed is 40.4 degrees. Among the three drift prediction models, the refined AP98 drift model demonstrates the highest forecasting precision. The findings of this study offer a more accurate drift prediction model for the search of an aircraft lost at sea. These results hold significant guiding importance for maritime search and rescue operations in the South China Sea.

First classification of iron meteorite fragment preserved in Chang’e-5 lunar soils - Xiaoying Liu; Lixin Gu; Heng-Ci Tian; Jing Li; Xu Tang; Sen Hu; Yangting Lin (Science Bulletin, 2024)

Rediscovery of Seriatopora corals in shallow reefs of Okinawa Island, Japan - Hideyuki Yamashiro; Sen-Lin Tang (Regional Studies in Marine Science, 2024)

Construction of copper-manganese based aminoclays with significant laccase-like activity and its prominent degradation performance towards bisphenol A - Yifan Zeng; Shiyong Sun; Rui Lv; Ke Wang; Yevgeny Aleksandrovich Golubev; Sen Lin; Faqin Dong; Elena Leonidovna Kotova; Olga Borisovna Kotova (Journal of Environmental Chemical Engineering, 2024)

Triclocarban exhibits higher adipogenic activity than triclosan through peroxisome proliferator-activated receptors pathways - Jia-Da Zhang; Sen He; Ting-Ting He; Chuan-Hai Li; Bing-Hua Yan; Yuan Yang; Jian Yang; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Environmental Pollution, 2024)

Desorption enhancement of aluminum-based adsorbent in lithium extraction from sulfate-type salt lakes - Yihong Guo; Jianguo Yu; Haiping Su; Sen Lin (Desalination, 2024)

Sulfur bacteria-reinforced microbial electrochemical denitrification - Sen Lin; Wentao Tang; Yihang Xiao; Feixiang Zan; Xiaoming Liu; Guanghao Chen; Tianwei Hao (Bioresource Technology, 2024)

A Spleen Tyrosine Kinase’s Sky in Neuronal Degeneration - Wan-Yun Zhang; Sen Lin (Neuroscience Bulletin, 2024)

Reciprocal transplant experiment reveals multiple factors influencing changes in coral microbial communities across climate zones - Ya-Fan Chan; Yu-Hsiang Chen; Sheng-Ping Yu; Hsing-Ju Chen; Yoko Nozawa; Sen-Lin Tang (Science of The Total Environment, 2024)

Late Holocene Climate Warming Events and Their Linkage to Hydraulic Engineering on the Coast of Hangzhou Bay, East China - Xunpeng Li; Xiaolei You; Sen Lin; Wentong Zhang; Zeen Cheng; Zhanghua Wang (Journal of Marine Science and Engineering, 2023)
The coastal lowlands in East China are very sensitive to climate change and marine disasters, and much large-scale hydraulic engineering was recorded in the historical documents of the Late Holocene. In this study, AMS 14C and OSL were used to date three sedimentary profiles from the north and south coasts of inner Hangzhou Bay, and grain size and geochemical analyses including organic carbon, macro-elements, and alkaline earth metals were performed, while hydraulic engineering records in historical documents were compiled, in an attempt to reveal the sedimentary records of extreme climatic and hydrological events over the past 3000 years and to probe into the correlation between them and hydraulic engineering. The results show that the intensified chemical weathering during ca. 200 BCE to 900 CE in East China corresponded to the warm and humid climate during the Qin-Han and Sui-Tang dynasties. Salinity intrusion with rising local water levels occurred in the lowland plains along the south coast of Hangzhou Bay from 120 to 895 CE. Low-salinity water intrusion from 32 to 488 CE was also recorded in the stratigraphy of lowland plains along the north coast of Hangzhou Bay. The sedimentary records of the East Tiaoxi River basin show river floods about 2000 years ago. The above sedimentary records indicate that the relative sea level rose in the Hangzhou Bay area during the Qin-Han and Sui-Tang Warm Periods, resulting in frequent salinity intrusion and river floods, which coincided with the historical records of hydraulic engineering such as the construction of seawalls, river levees, and the enclosure of lakes for restoration of river floods during the Han and Tang dynasties. Such coincidence reflects that climate change profoundly affected the hydrological environment of the coastal areas in East China as well as the response of the human societies.

Hormesis of glyphosate on ferulic acid metabolism and antifungal volatile production in rice root biocontrol endophyte Burkholderia cepacia LS-044 - Asif Hameed; Duc Hai Nguyen; Shih-Yao Lin; Paul Stothard; Poovarasan Neelakandan; Li-Sen Young; Chiu-Chung Young (Chemosphere, 2023)

Intrinsic peroxidase-like clay mineral nanozyme-triggered cascade bioplatform with enhanced catalytic performance - Ke Wang; Shiyong Sun; Yevgeny Aleksandrovich Golubev; Sen Lin; Jin Liu; Faqin Dong; Elena Leonidovna Kotova; Olga Borisovna Kotova (Applied Clay Science, 2023)

Combination of deep eutectic solvent and functionalized metal-organic frameworks as a green process for the production of 5-hydroxymethylfurfural and furfural from sugars - Quang Tam Huynh; Qing Huang; Shao-Yuan Leu; Yuan-Chung Lin; Chien-Sen Liao; Ken-Lin Chang (Chemosphere, 2023)

Improved functionality and safety of peptides by the formation of peptide-polyphenol complexes - Duanquan Lin; Le-Chang Sun; Wei-Sen Huo; Ling-Jing Zhang; Yu-Lei Chen; Song Miao; Min-Jie Cao (Trends in Food Science & Technology, 2023)

Effect of aggregation behavior on microplastic removal by magnetic Fe3O4 nanoparticles - Ruiqi Yan; Sen Lin; Weinan Jiang; Xia Yu; Lei Zhang; Wentao Zhao; Qian Sui (Science of The Total Environment, 2023)

A state-of-the-art analysis of pharmacological delivery and artificial intelligence techniques for inner ear disease treatment - Wanqing Li; Nan Zheng; Qiang Zhou; Mohammed S. Alqahtani; Dalia H. Elkamchouchi; Huajun Zhao; Sen Lin (Environmental Research, 2023)

Lithium extraction process from low grade Na+/K+ brines dependent on high layer charge layered double hydroxides - Bingchun Sheng; Haiping Su; Jianguo Yu; Sen Lin (Desalination, 2023)

Highly effective synthesis of 5-hydroxymethylfurfural from lignocellulosic biomass over a green and one-pot reaction in biphasic system - Quang Tam Huynh; Chong-Ting Zhong; Qing Huang; Yuan-Chung Lin; Ku-Fan Chen; Chien-Sen Liao; Cheng-Di Dong; Ken-Lin Chang (Bioresource Technology, 2023)

The Effect of Water Spinach on the Water Quality, Antioxidant System, Non-Specific Immune Response, Growth Performance, and Carbon Balance in Red Tilapia Production - Yuan-Yuan Luo; Xian-Can Chen; Rui-Lin Xie; Zhuo-Hao Ruan; Zhi-Qiang Lu; Liang-Sen Jiang; Yi-Fu Li; Wen-Sheng Liu (Fishes, 2023)
In this study, the compound aquaculture model of red tilapia (O. mossambicus albina × O. urolepis hornorum) and water spinach (Ipomoea aquatica) was used to investigate the effect of water spinach rafts on the water quality, antioxidant system, non-specific immune response, and growth performance of red tilapia and the carbon balance of payments. Red tilapia is characterized by its high adaptability to different production environments and food sources, as one of the most productive fish in aquaculture, and is well accepted in the market due to its nutritional and organoleptic characteristics. The experiment lasted for nine weeks and included two systems: the red tilapia-water spinach raft aquaponics (AP) system with 10% cover ratio with water spinach floating beds, and the aquatic monoculture (AM) system with only red tilapia. The total phosphorus (TP), total nitrogen (TN), and nitrate nitrogen (NO−3-N) in the AM were higher than those in AP from the fifth to ninth week. On the second, third, fifth, and sixth weeks, the ammonia nitrogen (NH4+-N), in the AM was higher than those in the AP. From the seventh week, the pH of the AM was significantly lower than the AP, while the nitrite nitrogen (NO−2-N) was significantly higher than the AP. The water quality index of the AP was better than that of the AM, indicating that water spinach can remove the nutrients from aquaculture water bodies. The average daily gain and specific growth rate (SGR) of fish in AP were higher than those in the AM. The acid phosphatase (ACP), alkaline phosphatase (AKP), and catalase (CAT) activities in the hepatopancreas of red tilapia in the AP were also significantly higher than those in the AM, while the malondialdehyde (MDA) in the AP was lower than the AM. The serum ACP and CAT of red tilapia in the AP were also higher than those in the AM, while the MDA of fish in the AP was lower than the AM. The results showed that both the experimental group and the control group were carbon sources and released greenhouse gases into the atmosphere, but the total carbon emissions of the red tilapia and the water spinach symbiotic system in the experimental group was significantly lower than that of the control group (p

Influence of different loads on PCDD/F removal by SCR during municipal solid waste incineration - Jiayao Wu; Yuxuan Ying; Yunfeng Ma; Sen Zheng; Xiaoqing Lin; Xiaodong Li; Jianhua Yan (Chemosphere, 2023)

Cost-effective one-spot hydrothermal synthesis of graphene oxide nanoparticles for wastewater remediation: AI-enhanced approach for transition metal oxides - Huang Zhongguan; Zhou Qiang; Lin Sen; Guodao Zhang; Ahmed Nadeem; Yisu Ge (Chemosphere, 2023)

Well-oriented immobilized immunoaffinity magnetic beads for detection of fumonisins in grains and feeds via pre-column automatic derivatization of high-performance liquid chromatography - Jinnan Chen; Meng Wang; Sen Li; Jin Ye; Li Li; Yu Wu; Di Cai; Tongtong Liu; Lin Zhu; Yi Shao; Songxue Wang (Food Chemistry, 2023)

Supplemental irrigation at the jointing stage of late sown winter wheat for increased production and water use efficiency - Sen Wang; Yuxi Niu; Li Shang; Zhenyan Li; Xiang Lin; Dong Wang (Field Crops Research, 2023)

Insight into intermediate impact of aging acidity and regulating mechanism on the performance of LiFePO4/C cathode material - Ting Zhang; Jianguo Yu; Sen Lin (Chemical Engineering Journal, 2023)

Application of water-saving irrigation and biostimulants on the agronomic performance of maize (Zea mays) - Cheng-Hsuan Chen; Kuan-Hung Lin; Yu-Sen Chang; Yu-Jie Chang (Process Safety and Environmental Protection, 2023)

From arc accretion to within-plate extension: Geochronology and geochemistry of the Neoproterozoic magmatism on the northern margin of the Yangtze Block - Yu Huang; Xiao-Lei Wang; Jun-Yong Li; Ru-Cao Li; De-Hong Du; Chang-Hong Jiang; Lin-Sen Li; Ning Ding (Precambrian Research, 2023)

The association between childhood adiposity in northeast China and anthropogenic heat flux: A new insight into the comprehensive impact of human activities - Hong-Zhi Zhang; Dao-Sen Wang; Si-Han Wu; Guo-Feng Huang; Duo-Hong Chen; Hui-Min Ma; Yun-Ting Zhang; Li-Hao Guo; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Therapy of spinal cord injury by zinc pyrogallol modified nanozyme via anti-inflammatory strategies - Wenxin Chen; Sen Lin; Yanfeng Shi; Qiang Guo; Yuanhong Xu; Yusheng Niu (Chemical Engineering Journal, 2023)

Adsorption of oxytetracycline on subalpine meadow soil from Zoige Plateau, China: Effects of the coexisting Cu2+ - Bin Wang; Jing Lin; Qicheng Hu; Fuyang Huang; Yan Huang; Weiguo Tu; Qingsong Chen; Sen Li (Environmental Research, 2023)

Experimental study on PSPC beam – Concrete encased CFST column frame installed with novel steel panel dampers - Yu Lin; Yifei Wang; Wuhong Wu; Sen Yang; Zhengxing Guo; Dongzhi Guan; Guojian Li (Engineering Structures, 2023)

A time-series analysis of short-term ambient ozone exposure and hospitalizations from acute myocardial infarction in Henan, China - Yulong Wei; Lin Fei; Yongbin Wang; Min Zhang; Zhigang Chen; Huige Guo; Shiqi Ge; Sen Zhu; Pingshuan Dong; Kan Yang; Na Xie; Guoan Zhao (Environmental Science and Pollution Research, 2023)
Epidemiological studies in recent years have identified an association between exposure to air pollutants and acute myocardial infarction (AMI); however, the association between short-term ozone (O 3 ) exposure and AMI hospitalization remains unclear, particularly in developing countries. Therefore, this study collected information on 24,489 AMI patients, including daily air pollutant and meteorological data in Henan, China, between 2016 and 2021. A distributed lagged nonlinear model combined with a Poisson regression model was used to estimate the nonlinear lagged effect of O 3 on AMI hospitalizations. We also quantified the effects of O 3 on the number of AMI hospitalizations, hospitalization days, and hospitalization costs. The results showed that single- and dual-pollution models of O 3 at lag0, lag1, and lag (01–07) were risk factors for AMI hospitalizations, with the most significant effect at lag03 (RR = 1.132, 95% CI:1.083–1.182). Further studies showed that males, younger people (15–64 years), warm seasons, and long sunshine duration were more susceptible to O 3 . Hospitalizations attributable to O 3 during the study period accounted for 11.66% of the total hospitalizations, corresponding to 2856 patients, 33,492 hospital days, and 90 million RMB. Maintaining O 3 at 10–130 µg/m 3 can prevent hundreds of AMI hospitalizations and save millions of RMB per year in Henan, China. In conclusion, we found that short-term exposure to O 3 was significantly associated with an increased risk of hospitalization for AMI in Henan, China, and that further reductions in ambient O 3 levels may have substantial health and economic benefits for patients and local healthcare facilities. Graphical Abstract

Culturing reef-building corals on a laboratory dish: a simple experimental platform for stony corals - Shinya Shikina; Tzu-Chieh Lin; Yu-Ling Chu; Yin-Chu Cheng; Yu-En Chang; Naohisa Wada; Sen-Lin Tang; Yoshiyuki Iizuka; Yi-Ling Chiu (Frontiers in Marine Science, 2023)
Development and maintenance of coral reef ecosystems rely on daily micro-biological activities of healthy corals. Although a comprehensive understanding of coral biological properties, as well as factors negatively affecting coral growth, are essential to conserve existing corals, the current lack of a tractable culture and experimental platform has delayed acquisition of such knowledge. Here we show a highly versatile culture system, “coral-on-a-laboratory dish” (CLD), allowing long-term culturing of various corals in plastic/glass Petri dishes with maintenance of their biological properties. Under optimized conditions, coral microcolonies (~5 mm x 5 mm fragments) of Pocillopora damicornis were cultured for several months in dishes with high survivorship and characteristic growth. These microcolonies maintained their biological properties, such as reproduction, skeleton formation, coral-algal symbiosis, ingestion, and digestion. Thus far, CLD has been used to maintain at least 4 other coral species from 4 other families, including the Acroporidae, the Pocilloporidae, the Poritidae, and the Merulinidae for more than 2 months with 100% survivorship. CLD is applicable to a variety of biophysiological studies, including coral-algal symbiosis and impact assessment of marine pollutants, e.g., a sunscreen substance, oxybenzone, and an organic biocide, Irgarol 1051, at cellular-level resolution. The CLD platform, which allows easy and inexpensive coral maintenance in a laboratory incubator, represents a technological breakthrough that will greatly advance coral studies.

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

A new sesquiterpene synthase catalyzing the formation of (R)-β-bisabolene from medicinal plant Colquhounia coccinea var. mollis and its anti-adipogenic and antibacterial activities - De-Sen Li; Lin-Lin Shi; Kai Guo; Shi-Hong Luo; Yan-Chun Liu; Yue-Gui Chen; Yan Liu; Sheng-Hong Li (Phytochemistry, 2023)

An accurate and efficient method for simultaneous determination of 16 trichothecenes in maize and wheat by UHPLC-Q-Orbitrap-HRMS combined one-step pretreatment with a novel isotope multipoint calibration strategy - Yu Wu; Jin Ye; Songshan Wang; Xiaomin Han; Li Li; Lin Zhu; Sen Li; Hongmei Liu; Yang Wang; Yi Shao; Songxue Wang (Food Control, 2023)

An optimization neural network model for bridge cable force identification - Tongtong Gai; Dehu Yu; Sen Zeng; Jerry Chun-Wei Lin (Engineering Structures, 2023)

TCRN: A Two-Step Underwater Image Enhancement Network Based on Triple-Color Space Feature Reconstruction - Sen Lin; Ruihang Zhang; Zemeng Ning; Jie Luo (Journal of Marine Science and Engineering, 2023)
The underwater images acquired by marine detectors inevitably suffer from quality degradation due to color distortion and the haze effect. Traditional methods are ineffective in removing haze, resulting in the residual haze being intensified during color correction and contrast enhancement operations. Recently, deep-learning-based approaches have achieved greatly improved performance. However, most existing networks focus on the characteristics of the RGB color space, while ignoring factors such as saturation and hue, which are more important to the human visual system. Considering the above research, we propose a two-step triple-color space feature fusion and reconstruction network (TCRN) for underwater image enhancement. Briefly, in the first step, we extract LAB, HSV, and RGB feature maps of the image via a parallel U-net-like network and introduce a dense pixel attention module (DPM) to filter the haze noise of the feature maps. In the second step, we first propose the utilization of fully connected layers to enhance the long-term dependence between high-dimensional features of different color spaces; then, a group structure is used to reconstruct specific spacial features. When applied to the UFO dataset, our method improved PSNR by 0.21% and SSIM by 0.1%, compared with the second-best method. Numerous experiments have shown that our TCRN brings competitive results compared with state-of-the-art methods in both qualitative and quantitative analyses.

Characteristics and provenances of rare earth elements and Nd isotopes in surface sediments of mangrove wetlands in the Jiulong River Estuary, China - Bo-sen Weng; Rui-an Wan; Rui-lian Yu; Gong-ren Hu; Yu Yan; Cheng-qi Lin; Hua-bin Huang (Environmental Science and Pollution Research, 2023)

Tomato recognition and location algorithm based on improved YOLOv5 - Tianhua Li; Meng Sun; Qinghai He; Guanshan Zhang; Guoying Shi; Xiaoming Ding; Sen Lin (Computers and Electronics in Agriculture, 2023)

A one-step regeneration method in-situ for deactivated aluminum-based lithium adsorbent used in high Mg2+/Li+ brines - Jun Chen; Jianglong Du; Jianguo Yu; Sen Lin (Desalination, 2023)

An injectable and rapidly degraded carboxymethyl chitosan/polyethylene glycol hydrogel for postoperative antiadhesion - Meiyue Wang; Sen Lin; Mengzhe Liu; Jing Jiao; Hongyan Mi; Jingjing Sun; Yiming Liu; Ruiying Guo; Sirui Liu; Haojie Fu; Yanyu Yang; Rui Li (Chemical Engineering Journal, 2023)

Identification of genetic loci associated with five agronomic traits in alfalfa using multi-environment trials - Sen Lin; Cesar A. Medina; Guojie Wang; David Combs; Glenn Shewmaker; Steve Fransen; Don Llewellyn; Steven Norberg; Long-Xi Yu (Theoretical and Applied Genetics, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Screening of marine Actinomycetia with bioactive metabolites from nearshore and deep sea marine sediments in southwestern Taiwan - Jimmy Kuo; Kuan-Ting Chen; Mei-Chin Lu; Ping-Jung Sung; Chorng-Horng Lin; Yung-Sen Huang (Biologia, 2023)

Transition of carbon-nitrogen coupling under different anthropogenic disturbances in subtropical small mountainous rivers - Li-Chin Lee; Gabriele Weigelhofer; Thomas Hein; Shin-Chien Chan; Ying-San Liou; Chien-Sen Liao; Fuh-Kwo Shiah; Yu-Lin Yu; Tsung-Yu Lee; Jr-Chuan Huang (Science of The Total Environment, 2023)

A novel methodological framework for risk zonation and source–sink response concerning heavy-metal contamination in agroecosystems - Lian Chen; Shenglu Zhou; Cuiming Tang; Guoqing Luo; Zhenjiang Wang; Sen Lin; Jianwu Zhong; Zhiyi Li; Yuan Wang (Science of The Total Environment, 2023)

Halogen microregulation in metal-organic frameworks for enhanced adsorption performance of ReO4-/TcO4- - Qing-Hua Hu; You-Gan Wang; Xin Gao; Yu-Zhen Shi; Sen Lin; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Combustion mechanism and ash-to-gas products of star anise residues: Atmosphere and temperature dependencies and joint optimization - Tao Chen; Xiaoming Li; Jiayu Liang; Fatih Evrendilek; Xiaocui Wen; Sen Lin; Jingyong Liu (Fuel, 2023)

Triclocarban and triclosan exacerbate high-fat diet-induced hepatic lipid accumulation at environmental related levels: The potential roles of estrogen-related receptors pathways - Xin Li; Jia-Da Zhang; Han Xiao; Sen He; Ting-Ting He; Xiao-Min Ren; Bing-Hua Yan; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Science of The Total Environment, 2023)

Studies on micromorphology and permeability of hydrate-bearing porous media - Gang Li; Yi-Fan Weng; Xiao-Sen Li; Ze-Lin Xu; Qiu-Nan Lv; Chun-Gang Xu (Fuel, 2023)

The tiered transaction system for sea use rights in China: Theoretical basis and market construction - Xuan Yu; Sen Lin; Weiteng Shen; Qi Chen (Marine Policy, 2023)

Concentrations, congener patterns, and correlations of unintentional persistent organic pollutants in cement kilns co-processing hazardous waste - Changzhi Chen; Haoyang Wang; Guorui Liu; Bingcheng Lin; Lili Yang; Rong Jin; Yuxiang Sun; Jianping Guo; Yinming Li; Nan Yang; Aihong Li; Changliang Li; et al. (Science of The Total Environment, 2023)

Bile acids and their receptors in regulation of gut health and diseases - Sen Lin; Sutian Wang; Peng Wang; Cuiming Tang; Zhenjiang Wang; Lian Chen; Guoqing Luo; Hong Chen; Yuntao Liu; Bin Feng; De Wu; Douglas G. Burrin; et al. (Progress in Lipid Research, 2023)

Enhancement of uniformity and performance of LiFePO4/C cathode material prepared via a continuous rotating reactor - Ting Zhang; Sen Lin; Jianguo Yu (Chemical Engineering Journal, 2023)

Migration, Health Risks, and Source Apportionment of Heavy Metals in Agricultural Soil–Dustfall–Crop Systems in a Typical Watershed of the Taihu Region, China - Lian Chen; Shenglu Zhou; Cuiming Tang; Guoqing Luo; Zhenjiang Wang; Sen Lin; Jianwu Zhong; Zhiyi Li; Yuan Wang (Water, Air, & Soil Pollution, 2023)

Study on the Coal–rock Ratio Effect of Asymmetric Deformation and Failure of the Gob–side Coal–rock Roadway in Gently Inclined Coal Seam - Lin Gao; Yexing Shen; Ping Liu; Yongyin Wang; Zhenqian Ma; Xiangtao Kang; Sen Han (Geotechnical and Geological Engineering, 2023)

Failure mode and genesis of bare dispersive soil slope in the cold dry region: insights from Southwest Songnen Plain, China - Yan Han; Qing Wang; Cencen Niu; Huicheng Fu; Jing Liu; Mengxia Han; Sen Lin; Muhammad Ammar (Bulletin of Engineering Geology and the Environment, 2022)

PLXDC2 enhances invadopodium formation to promote invasion and metastasis of gastric cancer cells via interacting with PTP1B - Bin Wu; Yan-xia Wang; Jun-jie Wang; Dong-fang Xiang; Meng-si Zhang; Ze-xuan Yan; Wen-ying Wang; Jing-ya Miao; Xi Lan; Jia-jia Liu; Zheng-yan Li; Chuan Li; et al. (Clinical & Experimental Metastasis, 2022)
Plexin-domain containing 2 (PLXDC2) has been reported as an oncoprotein in several human malignancies. However, its expression and roles in gastric cancer remain largely unclear. In this study, we found that PLXDC2 was highly expressed in gastric cancer tissues, and the expression levels were positively correlated with clinicopathological features, but negatively with the patients’ outcome. Cox regression analysis identified PLXDC2 as an independent prognostic indicator for the patients. Knockdown of PLXDC2 markedly suppressed the in vitro invasion and in vivo metastasis of gastric cancer cells, while overexpression of PLXDC2 resulted in opposite effects. Mechanistically, PLXDC2 enhanced the level of phosphorylated Cortactin (p-Cortactin) by physically interacting with protein tyrosine phosphatase 1B (PTP1B), an important dephosphorylase, to prevent its dephosphorylating of p-Cortactin, thereby promoting the formation of invadopodia. Collectively, our results indicate that PLXDC2 contributes to the invasion and metastasis of gastric cancer by inhibiting PTP1B to facilitate the invadopodium formation, and may serve as a potential prognostic biomarker and a therapeutic target for this disease.

A multi-step nitrifying microbial enrichment to remove ammonia and nitrite in brackish aquaculture systems - Dao Thi Anh Tuyet; Le Minh Hiep; Ha Thi Binh; Le Thanh Huyen; Sen-Lin Tang; Pei-Wen Chiang; Do Manh Hao (Biodegradation, 2022)

Arsenopyrite oxidative dissolution in NaCl solution at high-temperature and high-pressure conditions: kinetics, pathways, dissolution mechanism and geological implications - Qingyou Liu; Kai Zheng; Shuai Wang; Luying Wang; Sen Lin; Heping Li (Contributions to Mineralogy and Petrology, 2022)

Exploiting Sentinel-1 data and machine learning–based random forest for collectively mapping rice fields in Taiwan - Nguyen-Thanh Son; Chi-Farn Chen; Cheng-Ru Chen; Youg-Sin Cheng; Piero Toscano; Chein-Hui Syu; Horng-Yuh Guo; Shu-Ling Chen; Tsang-Sen Liu; Yi-Ting Zhang; Huan-Sheng Lin; Shih-Hsiang Chen; et al. (Applied Geomatics, 2022)

Shear Instability and Turbulent Mixing in the Stratified Shear Flow Behind a Topographic Ridge at High Reynolds Number - Jia-Lin Chen; Xiao Yu; Ming-Huei Chang; Sen Jan; Yiing Jang Yang; Ren-Chieh Lien (Frontiers in Marine Science, 2022)
Observations on the lee of a topographic ridge show that the turbulence kinetic energy (TKE) dissipation rate due to shear instabilities is three orders of magnitude higher than the typical value in the open ocean. Laboratory-scale studies at low Reynolds number suggest that high turbulent dissipation occurs primarily within the core region of shear instabilities. However, field-scale studies indicate that high turbulence is mainly populated along the braids of shear instabilities. In this study, a high-resolution, resolving the Ozmidov-scale, non-hydrostatic model with Large Eddy Simulation (LES) turbulent closure is applied to investigate dominant mechanisms that control the spatial and temporal scales of shear instabilities and resulting mixing in stratified shear flow at high Reynolds number. The simulated density variance dissipation rate is elevated in the cusp-like bands of shear instabilities with a specific period, consistent with the acoustic backscatter taken by shipboard echo sounder. The vertical length scale of each cusp-like band is nearly half of the vertical length scale of the internal lee wave. However, it is consistent with instabilities originating from a shear layer based on linear stability theory. The model results indicate that the length scale and/or the period of shear instabilities are the key parameters to the mixing enhancement that increases with lateral Froude number Fr L , i.e. stronger shear and/or steeper ridge.

Analysis of the influence of reinforcement material type on bearing and deformation characteristics of reinforced earth retaining wall - Jia-Quan Wang; Sen-Lei Hou; Zhi-Nan Lin; Yi Tang (Arabian Journal of Geosciences, 2022)

Composition, Demographic History, and Population Structures of Trichiurus - Kui-Ching Hsu; Mu-Rong Yi; Sui Gu; Xiong-Bo He; Zhi-Sen Luo; Bin Kang; Hung-Du Lin; Yun-Rong Yan (Frontiers in Marine Science, 2022)
Sequences of the complete mitochondrial cytochrome oxidase subunit I gene were used to identify Trichiurus species and examine their population genetic structure and demographic history along the coast of China. Three Trichiurus species were found. Trichiurus japonicus lives in colder waters along the continental shelves in the China Seas, while Trichiurus nanhaiensis lives warmer waters along continental slopes in the South China Sea, and Trichiurus brevis lives in shallow and warmer waters in the South China Sea. The migrations of these species were mainly associated with feeding and spawning preferences. Two major wintering and spawning grounds in the East China Sea and South China Sea were found. All species showed a lack of population genetic structure resulting from their oceanodromous life cycle (the degree of population substructure index N ST = 0.000–0.149), but the results of approximate Bayesian computational approaches suggested population declines or stabilization and differentiation. The results of the T MRCA (time to the most recent common ancestor) showed that during glaciations, the Yellow Sea and the East China Sea were completely exposed, and the South China Sea acted as a refugium. Thus, the populations of these three species experienced differentiation during glaciations. This study also examined the limitations of Bayesian skyline plot analysis.

Ocean Currents May Influence the Endolithic Bacterial Composition in Coral Skeletons - Po-Yu Liu; Sung-Yin Yang; Chih-Ying Lu; Naohisa Wada; Stéphane De Palmas; Shu-Shuo Yeh; Hideyuki Yamashiro; Sen-Lin Tang; Shan-Hua Yang (Frontiers in Marine Science, 2022)
Coral endolithic microbes can be an important nutrients support for hosts while under stresses. Previous studies have found that the endolithic microbial composition of a single coral species can be biogeographical diverse. However, the potential environmental factors, such as salinity, temperature, pH, and nutrient, that might influence the composition of the endolithic microbes remain unclear. In this study, we used both amplicon sequence variants (ASV) and a kmer-based taxonomic unit (KTU) to characterize the endolithic bacterial constitution of Isopora spp. located in the western Pacific Ocean—where it is subjected to the Kuroshio Current (in Okinawa, Japan and Green Island, Taiwan)—and the South China Sea (Dongsha Atoll). The endolithic bacterial community compositions showed a significant geographical difference, and we suggest that the ocean current and primary productivity are the most essential environmental factors influencing the bacterial communities in the skeleton of Isopora spp. In addition, our results showed that, technically, compared to ASV, bacterial composition based on KTU avoids extreme data, making it a suitable tool for explaining the associations between microbes and environmental factors.

Prevalence, complete genome, and metabolic potentials of a phylogenetically novel cyanobacterial symbiont in the coral‐killing sponge, Terpios hoshinota - Yu‐Hsiang Chen; Hsing‐Ju Chen; Cheng‐Yu Yang; Jia‐Ho Shiu; Daphne Z. Hoh; Pei‐Wen Chiang; Wenhua Savanna Chow; Chaolun Allen Chen; Tin‐Han Shih; Szu‐Hsien Lin; Chi‐Ming Yang; James Davis Reimer; et al. (Environmental Microbiology, 2022)
Summary Terpios hoshinota is an aggressive, space‐competing sponge that kills various stony corals. Outbreaks of this species have led to intense damage to coral reefs in many locations. Here, the first large‐scale 16S rRNA gene survey across three oceans revealed that bacteria related to the taxa Prochloron , Endozoicomonas , SAR116, Ruegeria , and unclassified Proteobacteria were prevalent in T . hoshinota . A Prochloron ‐related bacterium was the most dominant and prevalent cyanobacterium in T . hoshinota . The complete genome of this uncultivated cyanobacterium and pigment analysis demonstrated that it has phycobiliproteins and lacks chlorophyll b , which is inconsistent with the definition of Prochloron . Furthermore, the cyanobacterium was phylogenetically distinct from Prochloron , strongly suggesting that it should be a sister taxon to Prochloron . Therefore, we proposed this symbiotic cyanobacterium as a novel species under the new genus Candidatus Paraprochloron terpiosi. Comparative genomic analyses revealed that ‘Paraprochloron’ and Prochloron exhibit distinct genomic features and DNA replication machinery. We also characterized the metabolic potentials of ‘Paraprochloron terpiosi’ in carbon and nitrogen cycling and propose a model for interactions between it and T. hoshinota . This study builds a foundation for the study of the T . hoshinota microbiome and paves the way for better understanding of ecosystems involving this coral‐killing sponge.

A First Insight Into the Heat-Induced Changes in Proteomic Profiles of the Coral Symbiotic Bacterium Endozoicomonas montiporae - Ya-Fan Chan; Chia-Yu Chen; Chih-Ying Lu; Yung-Chi Tu; Kshitij Tandon; Shinya Shikina; Sen-Lin Tang (Frontiers in Marine Science, 2022)
Endozoicomonas , a core bacterial group in corals, may also be a coral symbiont. Endozoicomonas communities often decrease rapidly in corals under heat stress. However, how the bacteria respond to changes in temperature and coral host during heat stress is unknown. Here, we employed the cultivable, dominant species E. montiporae as a working organism to explore how Endozoicomonas responds to heat stress. We designed two experiments to clarify the extent to which E. montiporae is influenced by temperature and coral host. We detected differentially expressed protein (DEP) profiles in this bacterium at 31 and 33°C compared to 25°C by tandem mass tags-based quantitative proteome analysis. Fifty DEPs, including many heat shock proteins, were detected when the temperature changed. The expression of antioxidant defense proteins and key pyruvate synthase proteins decreased, suggesting that E. montiporae were in a physiology of stress at 33°C. Furthermore, some proteins were differentially expressed because of the heat-stress-treated coral lysate specifically, suggesting that not only heat but also heat-induced host factors can affect the protein expression of the bacterium. This study provides an in-depth analysis of how the molecular mechanisms of Endozoicomonas are affected by heat stress and coral host.

Multivariate analysis of the spatial species diversity of demersal fish assemblages in relation to habitat characteristics in a subtropical national park, Taiwan - Kuo-Shu Chen; Hsu-Sen Chen; Chiee-Young Chen; Yan-Lin Su; Pei-Jie Meng; Meng-Hsien Chen (Marine Biodiversity, 2022)
To understand the spatial species diversity of demersal fish assemblages in Taijiang National Park (TJNP) of Taiwan, fishes from 44 demersal trawl hauls and environmental data were collected in the nearshore and offshore areas of TJNP from April 2016 to May 2019. In total, fishes of 47 families, 84 genera, and 113 species were recorded. The nearshore and offshore demersal fish assemblages in TJNP exhibited significant variability in species composition assessed via beta diversity. Using distance-based redundancy analysis, we demonstrated that bottom depth and substrate type were significant explanatory variables of spatial species diversity and identified three habitat types (I: shallow soft bottom; II: deeper soft bottom; III: deeper bottom with mixed sand and gravel substrates). The nearshore assemblage was characterized by type I, where Tarphops oligolepis (flounder), Trachinocephalus myops (snakefish), and Liachirus melanospilos (carpet sole) dominated in terms of abundance. The offshore assemblage was characterized by either type II or type III because differences in substrate types among sampling sites were noticeable. At the offshore sites characterized by a deeper soft bottom (type II), Johnius distinctus (croaker), Cynoglossus kopsii (shortheaded tonguesole), and Coelorinchus formosanus (Formosa grenadier) predominated. In contrast, the westernmost sampling site, characterized by type III habitat, exhibited relatively high Shannon indices, and Scorpaena miostoma (scorpionfish), Urolophus aurantiacus (sepia stingray), and Parabothus taiwanensis (lefteye flounder) predominated. Our results provide the first baseline information on the environmental characteristics and spatial species diversity of demersal fish assemblages in TJNP and have implications for biodiversity conservation in existing spatial management areas.

Chemical constituents from the fruits of Piper longum L. and their vascular relaxation effect on rat mesenteric arteries - Dan Li; Rui Wang; Xiaohan Cheng; Jianfeng Yang; Yihui Yang; Huichong Qu; Sen Li; Shan Lin; Donghua Wei; Yuhua Bai; Xiaodong Zheng (Natural Product Research, 2022)

Investigating the Transcriptomic and Expression Presence-Absence Variation Exist in Japanese Eel (Anguilla japonica), a Primitive Teleost - Yung-Sen Huang; Chung-Yen Lin; Wen-Chih Cheng (Marine Biotechnology, 2021)

Experimental and Model Predictive Investigation into the Relationship of pH Alternation with Addition of Lime in Acid Tin Tailing Treatments - Feng Yin; Ying-Jie Li; Qun Zhao; Chen Li; Jie Li; Sen-Lin Tian (Bulletin of Environmental Contamination and Toxicology, 2021)

Negative‐pressure irrigation improves water and fertilizer use efficiencies and fruit yield of greenhouse tomato on the North China Plain* - Yinkun Li; Xuzhang Xue; Fan Xu; Wenzhong Guo; Minjie Duan; Sen Lin; Youli Li; Zhan Wang (Irrigation and Drainage, 2021)
Water and fertilizer supply are the main factors limiting greenhouse vegetable production on the North China Plain. This study tested the hypothesis that negative‐pressure irrigation is advantageous for reducing water and fertilizer application compared with drip irrigation in a greenhouse. Three treatments (drip irrigation + optimal fertilizer [DOF], drip irrigation + Yamazaki tomato nutrient solution [DNS], and negative‐pressure irrigation + Yamazaki tomato nutrient solution [NNS]) were applied in a greenhouse tomato double‐cropping system conducted in consecutive spring–summer and autumn–winter seasons. Soil moisture content, nitrate‐nitrogen (N) concentration, fruit yield, total N uptake ( N u ), irrigation water productivity, and partial factor productivity of applied fertilizer were analysed. The seasonal variation of soil moisture and nitrate‐N contents in the 0–20‐cm soil layer for NNS treatment was stable. Nitrate‐N accumulated after the final harvest in the autumn–winter season of NNS treatment was significantly less than under DOF and DNS. Despite lower water and nutrient inputs, NNS showed higher N u and fruit yield than DOF and DNS. These results demonstrated that negative‐pressure irrigation can reduce irrigation water and nutrient inputs and nitrate‐N accumulation in the soil, and significantly improve water and fertilizer use efficiency in greenhouse‐grown tomato compared with those under drip irrigation.

Phylogeography of Blue Corals (Genus Heliopora) Across the Indo-West Pacific - Hiroki Taninaka; Davide Maggioni; Davide Seveso; Danwei Huang; Abram Townsend; Zoe T. Richards; Sen-Lin Tang; Naohisa Wada; Taisei Kikuchi; Hideaki Yuasa; Megumi Kanai; Stéphane De Palmas; et al. (Frontiers in Marine Science, 2021)
Species delimitation of corals is one of the most challenging issues in coral reef ecology and conservation. Morphology can obscure evolutionary relationships, and molecular datasets are consistently revealing greater within-species diversity than currently understood. Most phylogenetic studies, however, have examined narrow geographic areas and phylogeographic expansion is required to obtain more robust interpretations of within- and among- species relationships. In the case of the blue coral Heliopora , there are currently two valid species ( H. coerulea and H. hiberniana ) as evidenced by integrated genetic and morphological analyses in northwestern Australia. There are also two distinct genetic lineages of H. coerulea in the Kuroshio Current region that are morphologically and reproductively different from each other. Sampling from all Heliopora spp. across the Indo-Pacific is essential to obtain a more complete picture of phylogeographic patterns. To examine phylogenetic relationships within the genus Heliopora , we applied Multiplexed inter simple sequence repeat (ISSR) Genotyping by sequencing (MIG-seq) on > 1287 colonies across the Indo-West Pacific. Maximum likelihood phylogenetic trees indicated the examined Heliopora samples comprise three genetically distinct groups: H. coerulea group, H. hiberniana group, and a new undescribed Heliopora sp. group with further subdivisions within each group. Geographic structuring is evident among the three species with H. hiberniana group found in the Indo-Malay Archipelago and biased toward the Indian Ocean whilst Heliopora sp. was only found in the Kuroshio Current region and Singapore, indicating that this taxon is distributed in the western Pacific and the Indo-Malay Archipelago. Heliopora coerulea has a wider distribution, being across the Indian Ocean and western Pacific. This study highlights the effectiveness of phylogenetic analysis using genome-wide markers and the importance of examining populations across their distribution range to understand localized genetic structure and speciation patterns of corals.

Geographic and subsequent biotic isolations led to a diversity anomaly of section Heterotropa (genus Asarum : Aristolochiaceae) in insular versus continental regions of the Sino‐Japanese Floristic Region - Daiki Takahashi; Shota Sakaguchi; Yu Feng; Yuji Isagi; Ying‐Xiong Qiu; Pan Li; Rui‐Sen Lu; Chang‐Tse Lu; Shih‐Wen Chung; Yang‐Shan Lin; Yun‐Chao Chen; Atsushi J. Nagano; et al. (Journal of Biogeography, 2021)
Aim The Sino‐Japanese Floristic Region has extremely high species diversity with respect to temperate plants; however, the reasons for this diversity are poorly understood because most studies have only considered geographic isolation caused by climatic oscillations. In some plant groups, high floral trait diversity and uneven species diversity between insular systems and the continental area suggest other factors may have important roles too. The primary purpose of this study is to reveal how abiotic and biotic factors have shaped the species diversity anomaly of Heterotropa between the insular systems and the continental area. Location The Sino‐Japanese Floristic Region. Taxon Section Heterotropa (genus Asarum ; Aristolochiaceae). Methods Using ddRAD‐seq and chloroplast genome data, we built a time‐calibrated phylogenetic tree including 79 species. We estimated the patterns of floral traits (flowering time and floral size) evolution using macroevolutionary modelling, and tested the correlation of speciation rate with the trait evolution rates. Finally, we estimated the isolation factors of all taxa pairs and sister‐taxa pairs based on distribution range and floral traits. Results Phylogenetic analysis indicated that Heterotropa was diverged into two clades (continental clade and insular clade) in the Miocene, and the major subclades corresponded to geographic entities. Most rate shifts accelerating floral trait's evolution occurred during the Pleistocene period. Evolution rate of floral traits showed positive correlation with the speciation rate. Large proportion of taxa in the insular clade are distributed allopatrically. Several sister pairs showed floral trait divergence with geographic overlap. Main Conclusions The diversification of Heterotropa appears to have been triggered by geographic and climatic events, and subsequent repeated floral trait evolution with and without geographic isolation. Furthermore, the high species diversity in the insular systems would have been formed by the repeated range fragmentations and contractions. Our study demonstrates the importance of multidimensional studies to understand the diversification process of temperate plants in the Sino‐Japanese Floristic Region.

Long‐term nitrogen input alters plant and soil bacterial, but not fungal beta diversity in a semiarid grassland - Weixing Liu; Lingli Liu; Xian Yang; Meifeng Deng; Zhou Wang; Pandeng Wang; Sen Yang; Ping Li; Ziyang Peng; Lu Yang; Lin Jiang (Global Change Biology, 2021)
Anthropogenic nitrogen (N) input is known to alter plant and microbial α‐diversity, but how N enrichment influences β‐diversity of plant and microbial communities remains poorly understood. Using a long‐term multilevel N addition experiment in a temperate steppe, we show that plant, soil bacterial and fungal communities exhibited different responses in their β‐diversity to N input. Plant β‐diversity decreased linearly as N addition increased, as a result of increased directional environmental filtering, where soil environmental properties largely explained variation in plant β‐diversity. Soil bacterial β‐diversity first increased then decreased with increasing N input, which was best explained by corresponding changes in soil environmental heterogeneity. Soil fungal β‐diversity, however, remained largely unchanged across the N gradient, with plant β‐diversity, soil environmental properties, and heterogeneity together explaining an insignificant fraction of variation in fungal β‐diversity, reflecting the importance of stochastic community assembly. Our study demonstrates the divergent effect of N enrichment on the assembly of plant, soil bacterial and fungal communities, emphasizing the need to examine closely associated fundamental components (i.e., plants and microorganisms) of ecosystems to gain a more complete understanding of ecological consequences of anthropogenic N enrichment.

Androgenic Sensitivities and Ovarian Gene Expression Profiles Prior to Treatment in Japanese Eel (Anguilla japonica) - Yung-Sen Huang; Wen-Chih Cheng; Chung-Yen Lin (Marine Biotechnology, 2021)

Monthly progression rates of the coral-killing sponge Terpios hoshinota in Sesoko Island, Okinawa, Japan - Siti N. Aini; Sen-Lin Tang; Hideyuki Yamashiro (Coral Reefs, 2021)

Impact factors of the accumulation, migration and spread of antibiotic resistance in the environment - Zibo Lin; Tao Yuan; Lai Zhou; Sen Cheng; Xu Qu; Ping Lu; Qiyan Feng (Environmental Geochemistry and Health, 2021)

Effects of plant growth regulators and polyamines on bract longevity in Bougainvillea buttiana - Kuan-Hung Lin; Jui-Mei Li; Chun-Wei Wu; Yu-Sen Chang (Horticulture, Environment, and Biotechnology, 2021)

Evaluation of the Possible Contribution of Phenylpropanoids to Potato Discoloration - Sen Lin; Moehninsi; Maximilian J. Feldman; Duroy A. Navarre (American Journal of Potato Research, 2021)

Shallow gas hydrates off southwest Taiwan and their mechanisms - Yin-Sheng Huang; Shu-Kun Hsu; Chih-Chieh Su; Andrew Tien-Shun Lin; Pai-Sen Yu; Nathalie Babonneau; Gueorgui Ratzov; Serge Lallemand; Pi-Chuen Huang; Shiao-Shan Lin; Jing-Yi Lin; Kuo-Yen Wei; et al. (Marine Geophysical Research, 2021)
We have collected two shallow gas hydrate samples at two sites having different geological settings off southwest Taiwan during the cruise MD214 in 2018. The first core site, MD18-3542, is on the South Yuan-An East Ridge at ~ 1200 m water deep, where a structural unconformity covered by fine-silt sediments appears at ~ 5.5 m below the seafloor. The second core site, MD18-3543, is close to the Good-Weather Ridge at ~ 1100 m water deep, where a gas-related pockmark structure and authigenic carbonates are present at shallow strata with fine-silt sediments near the seafloor. Sediment properties of core MD18-3542 are distinctively different above and below the layer corresponding to the unconformity. Both cores show obvious gaps or voids in the lower core halves. The core features could be linked to the dissociated methane upward migrating from deep strata. Core site settings with upwelling methane would favor the formation of shallow gas hydrates. At site MD18-3542, the shallow hydrate could be formed due to high concentration methane kept beneath the unconformity covered by fine-silt sediments. At site MD18-3543, the shallow hydrate could be formed due to an extremely high flux of upwelling methane trapped either beneath the authigenic carbonates or fine-silt sediments.

Model test on support scheme for carbonaceous slate tunnel in high geostress zone at high depth - Zhi-gang Tao; Shu-lin Ren; Gan Li; Hao-tian Xu; Sen-lin Luo; Man-chao He (Journal of Mountain Science, 2021)

Effects of Ocean Acidification on Coral Endolithic Bacterial Communities in Isopora palifera and Porites lobata - Sung-Yin Yang; Chih-Ying Lu; Sen-Lin Tang; Rocktim Ramen Das; Kazuhiko Sakai; Hideyuki Yamashiro; Shan-Hua Yang (Frontiers in Marine Science, 2020)
Endolithic microbes in coral reefs may act as a nutrient source for their coral hosts. Increasing atmospheric CO 2 concentrations are causing ocean acidification (OA), which may affect marine organisms and ecosystems, especially calcifying organisms such as reef-building corals. However, knowledge of how OA affects marine microbes remains limited, and little research has been done on how coral endolithic communities respond to shifting environmental baselines. In this study, the endolithic communities of two common shallow water coral species, Isopora palifera and Porites lobata , were examined to investigate the microbial community dynamics under OA treatments. The colonies were placed in an environment with a partial pressure of carbon dioxide ( p CO 2 ) of 1,000 or 400 ppm (control) for 2 months. Several I. palifera colonies bleached and died at 1,000 ppm p CO 2 , but the P. lobata colonies remained unaffected. Inversely, the endolithic community in P. lobata skeletons showed significant changes after OA treatment, whereas no significant dynamics were observed among the I. palifera endoliths. Our findings suggest that the skeletal structures of different coral species may play a key role in corals host and endoliths under future high-OA scenarios.

Overexpression of LncRNA PSMG3-AS1 Distinguishes Glioblastomas from Sarcoidosis - Liusheng Chen; Guanliang Wang; Zihui Xu; Kailong Lin; Sen Mu; Yicheng Pan; Mengya Shan (Journal of Molecular Neuroscience, 2020)

Visuospatial Memory Alteration in Alzheimer’s Disease - Sen Lin (Neuroscience Bulletin, 2020)

Development of in-situ Micro-Raman spectroscopy system for autoclave experimental apparatus - Lin Chen; Heping Li; Shengbin Li; Liping Xu; Sen Lin; Hongbin Zhou (Acta Geochimica, 2020)

Critical transition of soil bacterial diversity and composition triggered by nitrogen enrichment - Weixing Liu; Lin Jiang; Sen Yang; Zhou Wang; Rui Tian; Ziyang Peng; Yongliang Chen; Xingxu Zhang; Jialiang Kuang; Ning Ling; Shaopeng Wang; Lingli Liu (Ecology, 2020)
Soil bacterial communities are pivotal in regulating terrestrial biogeochemical cycles and ecosystem functions. The increase in global nitrogen (N) deposition has impacted various aspects of terrestrial ecosystems, but we still have a rudimentary understanding of whether there is a threshold for N input level beyond which soil bacterial communities will experience critical transitions. Using high‐throughput sequencing of the 16S rRNA gene, we examined soil bacterial responses to a long‐term (13 yr), multi‐level, N addition experiment in a temperate steppe of northern China. We found that plant diversity decreased in a linear fashion with increasing N addition. However, bacterial diversity responded nonlinearly to N addition, such that it was unaffected by N input below 16 g N·m −2 ·yr −1 , but decreased substantially when N input exceeded 32 g N·m −2 ·yr −1 . A meta‐analysis across four N addition experiments in the same study region further confirmed this nonlinear response of bacterial diversity to N inputs. Substantial changes in soil bacterial community structure also occurred between N input levels of 16 to 32 g N·m −2 ·yr −1 . Further analysis revealed that the loss of soil bacterial diversity was primarily attributed to the reduction in soil pH, whereas changes in soil bacterial community were driven by the combination of increased N availability, reduced soil pH, and changes in plant community structure. In addition, we found that N addition shifted bacterial communities toward more putatively copiotrophic taxa. Overall, our study identified a threshold of N input level for bacterial diversity and community composition. The nonlinear response of bacterial diversity to N input observed in our study indicates that although bacterial communities are resistant to low levels of N input, further increase in N input could trigger a critical transition, shifting bacterial communities to a low‐diversity state.

Supportive role of the Na+ transporter CmHKT1;1 from Cucumis melo in transgenic Arabidopsis salt tolerance through improved K+/Na+ balance - Li-Wei Gao; Sen-Lin Yang; Shi-Wei Wei; Dan-Feng Huang; Yi-Dong Zhang (Plant Molecular Biology, 2020)

Enhanced Antitumor Efficacy of Curcumin-Loaded PLGA Nanoparticles Coated with Unique Fungal Hydrophobin - Lu Sun; Hui Xu; Jing-hua Xu; Shao-ning Wang; Jun-wei Wang; Hong-feng Zhang; Wei-ru Jia; Lin-sen Li (AAPS PharmSciTech, 2020)

Influencing factors of consumers’ willingness to purchase green housing: a survey from Shandong Province, China - Peidong Sang; Haona Yao; Lin Zhang; Sen Wang; Yanjie Wang; Jinjian Liu (Environment, Development and Sustainability, 2020)

NLRP3 Deficiency Attenuates Secondary Degeneration of Visual Cortical Neurons Following Optic Nerve Injury - Zhou Zhang; Wenyi Liu; Yubin Huang; Linlin Luo; Xiaofeng Cai; Yunjia Liu; Liqianyu Ai; Jun Yan; Sen Lin; Jian Ye (Neuroscience Bulletin, 2020)

Erratum to: Exosome-derived galectin-9 may be a novel predictor of rejection and prognosis after liver transplantation - Ai-bin Zhang; Yi-fan Peng; Jun-jun Jia; Yu Nie; Shi-yu Zhang; Hai-yang Xie; Lin Zhou; Shu-sen Zheng (Journal of Zhejiang University-SCIENCE B, 2020)

Resource availability affects temporal variation of phytoplankton size structure in the Kuroshio east of Taiwan - Fan‐Sian Lin; Pei‐Chi Ho; Akash R. Sastri; Chung‐Chi Chen; Gwo‐Ching Gong; Sen Jan; Chih‐hao Hsieh (Limnology and Oceanography, 2020)
The on‐going discussion concerning how environmental factors determine phytoplankton size structure has centered around two hypotheses: (H1) The resource‐size relationship predicts that normalized biovolume size spectrum (NBSS) slopes for phytoplankton are progressively shallower with increasing resource availability and (H2) The temperature‐size relationship predicts that phytoplankton NBSS slopes steepen with increasing water temperature. To test these hypotheses, we examined 72 phytoplankton assemblage collections in the Kuroshio east of Taiwan. Total phytoplankton biomass was used as a proxy for resource availability instead of nutrients because nutrients are depleted and do not represent resource availability for oligotrophic seas. We found no significant relationship between NBSS slopes with temperature, providing little support for the temperature‐size rule. In contrast, a positive relationship between NBSS slopes and total biomass for most of the year lends general support to the resource‐size relationship, except during the winter and early spring. To explain this exception, we hypothesize that resource pulses occurring during the cold seasons are used more efficiently by small cells and promote faster growth of small relative to large phytoplankton because these pulses take place after a long period of resource depletion in oligotrophic seas; thus, the NBSS slopes become much steeper than would be expected from a positive resource‐size relationship. This deviation can be considered as nonsteady state in terms of phytoplankton size structure relative to resources. Nevertheless, we cannot rule out the possibility that grazing effects also play an important role in controlling phytoplankton size structure.

EFFECT OF A ROOT‐ZONE INJECTION IRRIGATION METHOD ON WATER PRODUCTIVITY AND APPLE PRODUCTION IN A SEMI‐ARID REGION IN NORTH‐WESTERN CHINA - Yan‐Ping Wang; Lin‐Sen Zhang; Yan Mu; Wei‐Hong Liu; Fu‐Xing Guo; Tian‐Ran Chang (Irrigation and Drainage, 2020)
Within the Chinese Loess Plateau, water resources are scarce and irrigation efficiency is a challenging issue. Traditional surface drip irrigation (SDI) methods have failed to improve irrigation efficiency and reduce surface evaporation in the region. An easy‐to‐install and practicable root‐zone injection irrigation (RII) method, with a low risk of emitter clogging and which uses subsurface infiltration‐promoting apparatuses (SIPA) to deliver water directly to the root zone, was designed and tested in an apple orchard over 3 years in northern Shaanxi, China. In the 0–0.6 m soil layer (where the apple roots are concentrated), the RII method produced consistently higher soil water content than the SDI method over all three growing seasons. The soil water content was consistently higher than 60% of field capacity, thus meeting the water requirements of fruit‐bearing apple trees. In addition, the RII method alleviated soil desiccation, significantly increased apple yields and improved fruit quality compared with the SDI method using the same volume of irrigation water. Both irrigation efficiency and water‐use efficiency were improved with the RII method. These results provide a theoretical basis for the utilization of the RII irrigation method in apple orchards in semi‐arid regions, which may improve water conservation and the sustainability of apple production. © 2019 John Wiley & Sons, Ltd.

Correction to: Soluble Epoxide Hydrolase Inhibition Attenuates Excitotoxicity Involving 14,15-Epoxyeicosatrienoic Acid–Mediated Astrocytic Survival and Plasticity to Preserve Glutamate Homeostasis - Yi-Min Kuo; Pei-Chien Hsu; Chia-Chi Hung; Ya-Yu Hu; Yu-Jie Huang; Yu-Ling Gan; Chun-Hua Lin; Feng-Shiun Shie; Wen-Kuei Chang; Lung-Sen Kao; Mei-Yung Tsou; Yi-Hsuan Lee (Molecular Neurobiology, 2019)

Soluble Epoxide Hydrolase Inhibition Attenuates Excitotoxicity Involving 14,15-Epoxyeicosatrienoic Acid–Mediated Astrocytic Survival and Plasticity to Preserve Glutamate Homeostasis - Yi-Min Kuo; Pei-Chien Hsu; Chia-Chi Hung; Ya-Yu Hu; Yu-Jie Huang; Yu-Ling Gan; Chun-Hua Lin; Feng-Shiun Shie; Wen-Kuei Chang; Lung-Sen Kao; Mei-Yung Tsou; Yi-Hsuan Lee (Molecular Neurobiology, 2019)

Removal of aqueous fluoroquinolones with multi-functional activated carbon (MFAC) derived from recycled long-root Eichhornia crassipes: batch and column studies - Lili Liu; Xin Chen; Zhiping Wang; Sen Lin (Environmental Science and Pollution Research, 2019)

Perineuronal Nets Restrict the Induction of Long-Term Depression in the Mouse Hippocampal CA1 Region - Guan Hock Khoo; Yu-Ting Lin; Tsung-Chih Tsai; Kuei-Sen Hsu (Molecular Neurobiology, 2019)

Rab18 Collaborates with Rab7 to Modulate Lysosomal and Autophagy Activities in the Nervous System: an Overlapping Mechanism for Warburg Micro Syndrome and Charcot-Marie-Tooth Neuropathy Type 2B - Fang-Shin Nian; Lei-Li Li; Chih-Ya Cheng; Pei-Chun Wu; You-Tai Lin; Cheng-Yung Tang; Bo-Shiun Ren; Chin-Yin Tai; Ming-Ji Fann; Lung-Sen Kao; Chen-Jee Hong; Jin-Wu Tsai (Molecular Neurobiology, 2019)

Global Perspectives on Observing Ocean Boundary Current Systems - Robert E. Todd; Francisco P. Chavez; Sophie Clayton; Sophie Cravatte; Marlos Goes; Michelle Graco; Xiaopei Lin; Janet Sprintall; Nathalie V. Zilberman; Matthew Archer; Javier Arístegui; Magdalena Balmaseda; et al. (Frontiers in Marine Science, 2019)

The analysis of clinical and laboratory data: a large outbreak of dengue fever in Chaozhou, Guangdong province, China - Fen Lin; Hui Yang; Lin Zhang; Sen-Hai Fang; Xiao-Fen Zhan; Li-Ye Yang (Archives of Virology, 2019)

Exosome-derived galectin-9 may be a novel predictor of rejection and prognosis after liver transplantation - Ai-bin Zhang; Yi-fan Peng; Jun-jun Jia; Yu Nie; Shi-yu Zhang; Hai-yang Xie; Lin Zhou; Shu-sen Zheng (Journal of Zhejiang University-SCIENCE B, 2019)

Lasiodiplodia spp. associated with Aquilaria crassna in Laos - Yu Wang; Sen Lin; Lin Zhao; Xiang Sun; Wei He; Ying Zhang; Yu-Cheng Dai (Mycological Progress, 2019)

Magma–magma interaction in the mantle recorded by megacrysts from Cenozoic basalts in eastern China - Xun Yu; Gang Zeng; Li-Hui Chen; Sen-Lin Hu; Zhi-Qiang Yu (International Geology Review, 2019)

Island soil quality assessment and the relationship between soil quality and land-use type/topography - Xia Lu; Yuanzhi Zhang; Yali Lin; Sen Zhang; Qian Zhao (Environmental Monitoring and Assessment, 2019)

Tropical Pacific Observing System - Neville Smith; William S. Kessler; Sophie Cravatte; Janet Sprintall; Susan Wijffels; Meghan F. Cronin; Adrienne Sutton; Yolande L. Serra; Boris Dewitte; Peter G. Strutton; Katherine Hill; Alex Sen Gupta; et al. (Frontiers in Marine Science, 2019)

Polymorphism of duck MHC class molecules - Lin Zhang; Dongmei Lin; Sen Yu; Junping Bai; Wanchun Jiang; Wenzheng Su; Yanyan Huang; Shaohua Yang; Jiaqiang Wu (Immunogenetics, 2019)

Fibroblast growth factor 10 (FGF10) promotes the adipogenesis of intramuscular preadipocytes in goat - Qing Xu; Sen Lin; Yong Wang; Jiangjiang Zhu; Yaqiu Lin (Molecular Biology Reports, 2018)

Study on Distribution Characteristics of Mining Stress and Elastic Energy Under Hard and Thick Igneous Rocks - Jin-quan Jiang; Quan-sen Wu; Quan-lin Wu; Pu Wang; Chen Zhang; Bin Gong (Geotechnical and Geological Engineering, 2018)

IgA nephropathy: clearance kinetics of IgA-containing immune complexes - Ann Chen; Sung-Sen Yang; Tsai-Jung Lin; Shuk-Man Ka (Seminars in Immunopathology, 2018)

The coexistence of copy number variations (CNVs) and single nucleotide polymorphisms (SNPs) at a locus can result in distorted calculations of the significance in associating SNPs to disease - Jiaqi Liu; Yangzhong Zhou; Sen Liu; Xiaofei Song; Xin-Zhuang Yang; Yanhui Fan; Weisheng Chen; Zeynep Coban Akdemir; Zihui Yan; Yuzhi Zuo; Renqian Du; Zhenlei Liu; et al. (Human Genetics, 2018)

Genotype imputation for Han Chinese population using Haplotype Reference Consortium as reference - Yuan Lin; Lu Liu; Sen Yang; Yun Li; Dongxin Lin; Xuejun Zhang; Xianyong Yin (Human Genetics, 2018)

Using network to enhance the insights on correlation and pollution assessment of co-occurring metals in marine sediments, the East China Sea - Lili Liu; Yupeng Wang; Sen Lin; Hong Li; Xin Chen; Zhiping Wang; Kuangfei Lin (Environmental Science and Pollution Research, 2018)

Coralloluteibacterium stylophorae gen. nov., sp. nov., a new member of the family Lysobacteraceae isolated from the reef-building coral Stylophora sp. - Wen-Ming Chen; Pei-Bei Xie; Sen-Lin Tang; Shih-Yi Sheu (Archives of Microbiology, 2018)

Calcification response of Pleurochrysis carterae to iron concentrations in batch incubations: implication for the marine biogeochemical cycle - Xiang Zou; Shiyong Sun; Sen Lin; Kexuan Shen; Faqin Dong; Daoyong Tan; Xiaoqin Nie; Mingxue Liu; Jie Wei (Frontiers of Earth Science, 2017)

ACOS5 is required for primexine formation and exine pattern formation during microsporogenesis in Arabidopsis - Hui-hui Xie; Lin Chen; Fa-qing Xu; Wan-sheng Guo; Shui Wang; Zhong-nan Yang; Sen Zhang (Journal of Plant Biology, 2017)

Metformin Improves Functional Recovery After Spinal Cord Injury via Autophagy Flux Stimulation - Di Zhang; Jun Xuan; Bin-bin Zheng; Yu-long Zhou; Yan Lin; Yao-sen Wu; Yi-fei Zhou; Yi-xing Huang; Quan Wang; Li-yan Shen; Cong Mao; Yan Wu; et al. (Molecular Neurobiology, 2017)

Distance-dependent varieties of microbial community structure and metabolic functions in the rhizosphere of Sedum alfredii Hance during phytoextraction of a cadmium-contaminated soil - Wenhao Yang; Taoxiang Zhang; Sen Lin; Wuzhong Ni (Environmental Science and Pollution Research, 2017)

N2O emission characteristics and its affecting factors in rain-fed potato fields in Wuchuan County, China - Liwei Wang; Cheng Wang; Zhihua Pan; Hui Xu; Lin Gao; Peiyi Zhao; Zhiqiang Dong; Jingting Zhang; Guohui Cui; Sen Wang; Guolin Han; hui Zhao (International Journal of Biometeorology, 2017)

Important Roles of Ring Finger Protein 112 in Embryonic Vascular Development and Brain Functions - Jen-Hui Tsou; Ying-Chen Yang; Ping-Chieh Pao; Hui-Ching Lin; Nai-Kuei Huang; Shih-Ting Lin; Kuei-Sen Hsu; Che-Ming Yeh; Kuen-Haur Lee; Chu-Jen Kuo; De-Ming Yang; Jiann-Her Lin; et al. (Molecular Neurobiology, 2017)

Enhanced production of fructosyltransferase in Aspergillus oryzae by genome shuffling - Shenghai Wang; Mengjie Duan; Yalan Liu; Sen Fan; Xiaoshan Lin; Yi Zhang (Biotechnology Letters, 2017)

Association Between Plasminogen Activator Inhibitor-1 Genetic Polymorphisms and Stroke Susceptibility - Xin Hu; Xin Zan; Zhiyi Xie; Yunke Li; Sen Lin; Hao Li; Chao You (Molecular Neurobiology, 2017)

NanoSIMS imaging method of zircon U-Pb dating - Sen Hu; YangTing Lin; Wei Yang; Wei-RZ Wang; JianChao Zhang; JiaLong Hao; WeiFan Xing (Science China Earth Sciences, 2016)

Allergy symptoms, serum total immunoglobulin E, and risk of head and neck cancer - Hsiao-Chen Liao; Shang-Yin Wu; Chun-Yen Ou; Jenn-Ren Hsiao; Jehn-Shyun Huang; Sen-Tien Tsai; Cheng-Chih Huang; Tung-Yiu Wong; Wei-Ting Lee; Ken-Chung Chen; Sheen-Yie Fang; Jiunn-Liang Wu; et al. (Cancer Causes & Control, 2016)

Comparison of vitrified outcomes between human early blastocysts and expanded blastocysts - Wen-yan Song; Xue-gai Wang; Hai-xia Jin; Gui-dong Yao; Xiang-yang Zhang; Sen-lin Shi; Hong-yi Yang; Zhao-feng Peng; Ying-pu Sun (In Vitro Cellular & Developmental Biology - Animal, 2016)

Prevalence of potential nitrogen‐fixing, green sulfur bacteria in the skeleton of reef‐building coral I sopora palifera - Shan‐Hua Yang; Sonny T. M. Lee; Chang‐Rung Huang; Ching‐Hung Tseng; Pei‐Wen Chiang; Chung‐Pin Chen; Hsing‐Ju Chen; Sen‐Lin Tang (Limnology and Oceanography, 2016)
Microbial endoliths, which inhabit interior pores of rocks, skeletons and coral, are ubiquitous in terrestrial and marine environments. In this study, various colored layers stratified the endolithic environment within the skeleton of Isopora palifera ; however, there was a distinct green‐pigmented layer in the skeleton (beneath the living coral tissue). To characterize diversity of endolithic microorganisms, 16S ribosomal RNA gene amplicon pyrosequencing was used to investigate bacterial communities in the green layer of eight I. palifera coral colonies retrieved from two locations on Green Island, Taiwan. The dominant bacterial group in the green layer belonged to the bacterial phylum Chlorobi, green sulfur bacteria capable of anoxygenic photosynthesis and nitrogen fixation. Specifically, bacteria of the genus Prosthecochloris were dominant in this green layer. To our knowledge, this is the first study to provide a detailed profile of endolithic bacteria in coral and to determine the prevalence of Prosthecochloris in the green layer. Based on our findings, we infer that these bacteria may have an important functional role in the coral holobiont in the nutrient‐limited coral reef ecosystem.

Inhibition of Autophagy by Estradiol Promotes Locomotor Recovery after Spinal Cord Injury in Rats - Chao-Wei Lin; Bi Chen; Ke-Lun Huang; Yu-Sen Dai; Hong-Lin Teng (Neuroscience Bulletin, 2016)

Identification of cell types, tissues and pathways affected by risk loci in psoriasis - Yan Lin; Pan Zhao; Changbing Shen; Songke Shen; Xiaodong Zheng; Xianbo Zuo; Sen Yang; Xuejun Zhang; Xianyong Yin (Molecular Genetics and Genomics, 2016)

Phosphorus-controlled trace element distribution in zircon revealed by NanoSIMS - Wei Yang; Yangting Lin; Jialong Hao; Jianchao Zhang; Sen Hu; Huaiwei Ni (Contributions to Mineralogy and Petrology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

A simple method to extract tropical monsoon forests using NDVI based on MODIS data: A case study in South Asia and Peninsula Southeast Asia - Sen Lin; Ronggao Liu (Chinese Geographical Science, 2016)

NanoSIMS analytical technique and its applications in earth sciences - Wei Yang; Sen Hu; JianChao Zhang; JiaLong Hao; YangTing Lin (Science China Earth Sciences, 2015)

Ecological status classification of the Taizi River Basin, China: a comparison of integrated risk assessment approaches - Juntao Fan; Elena Semenzin; Wei Meng; Elisa Giubilato; Yuan Zhang; Andrea Critto; Alex Zabeo; Yun Zhou; Sen Ding; Jun Wan; Mengchang He; Chunye Lin (Environmental Science and Pollution Research, 2015)

Response of shoot growth, photosynthetic capacity, flowering, and fruiting of potted ‘Nagami’ kumquat to different regulated deficit irrigation - Yung-Chiung Chang; Yu-Sen Chang; Lian-Hsiung Lin (Horticulture, Environment, and Biotechnology, 2015)

Assessing the authenticity of commercial deep-sea drinking water by chemical and isotopic approaches - Tsung-Ren Peng; Wen-Jui Liang; Tsang-Sen Liu; Yu-Wen Lin; Wen-Jun Zhan (Isotopes in Environmental and Health Studies, 2015)

Association between the CYP2E1 polymorphisms and lung cancer risk: a meta-analysis - Xiang-Hua Ye; Liang Song; Ling Peng; Zhibin Bu; Sen-Xiang Yan; Jie Feng; Xin-Li Zhu; Xin-Biao Liao; Xue-Lin Yu; Danfang Yan (Molecular Genetics and Genomics, 2015)

Cell-density-dependent manifestation of partial characteristics for neuronal precursors in a newly established human gliosarcoma cell line - Pei-Sen Yao; De-Zhi Kang; Xing-Fu Wang; Ru-Ying Lin; Zu-Cheng Ye (In Vitro Cellular & Developmental Biology - Animal, 2015)

Characterization of Single-Walled Carbon Nanotubes and Adsorption of Perchlorate in Water - Yung-Sen Hsu; Jie-Chung Lou; Ming-Shean Chou; Kai-Lin Hsu; Jia-Yun Han (Water, Air, & Soil Pollution, 2015)

Oricola cellulosilytica gen. nov., sp. nov., a cellulose-degrading bacterium of the family Phyllobacteriaceae isolated from surface seashore water, and emended descriptions of Mesorhizobium loti and Phyllobacterium myrsinacearum - Asif Hameed; Mariyam Shahina; Wei-An Lai; Shih-Yao Lin; Li-Sen Young; You-Cheng Liu; Yi-Han Hsu; Chiu-Chung Young (Antonie van Leeuwenhoek, 2015)

Spatial and temporal variation characteristics of ocean waves in the South China Sea during the boreal winter - Geli Zhu; Wantao Lin; Sen Zhao; Yanhua Cao (Acta Oceanologica Sinica, 2015)

A Brassica napus PHT1 phosphate transporter, BnPht1;4, promotes phosphate uptake and affects roots architecture of transgenic Arabidopsis - Feng Ren; Cai-Zhi Zhao; Chun-Sen Liu; Ke-Lin Huang; Qian-Qian Guo; Li-Li Chang; Huan Xiong; Xue-Bao Li (Plant Molecular Biology, 2014)

Classification and identification of metal-accumulating plant species by cluster analysis - Wenhao Yang; He Li; Taoxiang Zhang; Lin Sen; Wuzhong Ni (Environmental Science and Pollution Research, 2014)

Naphtho[1,2-b]furan-4,5-dione inhibits MDA-MB-231 cell migration and invasion by suppressing Src-mediated signaling pathways - Pei-Chien Tsai; Chiao-Lun Chu; Yaw-Syan Fu; Chih-Hua Tseng; Yeh-long Chen; Long-Sen Chang; Shinne-Ren Lin (Molecular and Cellular Biochemistry, 2014)

Use of motor abundance in old adults in the regulation of a narrow-based stance - Wei-Li Hsu; Kwan-Hwa Lin; Rong-Sen Yang; Chih-Hsiu Cheng (European Journal of Applied Physiology, 2014)

Two new ursolic acid saponins from Morina nepalensis var. alba Hand-Mazz - Zhi-feng Zhang; Lu-yang Lu; Pei Luo; Lin-sen Qing; Yuan Liu (Natural Product Research, 2013)

The short chain cell-permeable ceramide (C6) restores cell apoptosis and perifosine sensitivity in cultured glioblastoma cells - Li-sen Qin; Zheng-quan Yu; Shi-ming Zhang; Guan Sun; Jian Zhu; Jin Xu; Jun Guo; Lin-shan Fu (Molecular Biology Reports, 2013)

Warnstorfia exannulata, an aquatic moss in the Arctic: seasonal growth responses - Cai-Qing Guo; Ryszard Ochyra; Peng-Cheng Wu; Rodney D. Seppelt; Yi-Feng Yao; Lin-Gen Bian; Su-Ping Li; Cheng-Sen Li (Climatic Change, 2013)

Folic acid inhibits endothelial cell proliferation through activating the cSrc/ERK 2/NF-κB/p53 pathway mediated by folic acid receptor - Shyr-Yi Lin; Woan-Ruoh Lee; Yi-Fan Su; Sung-Po Hsu; Hsu-Chen Lin; Pei-Yin Ho; Tien-Chi Hou; Yu-Pei Chou; Chun-Ting Kuo; Wen-Sen Lee (Angiogenesis, 2012)

Strengthening of paleo‐typhoon and autumn rainfall in Taiwan corresponding to the Southern Oscillation at late Holocene - Huei‐Fen Chen; Shie‐Ying Wen; Shen‐Rong Song; Tien‐Nan Yang; Teh‐Quei Lee; Sue‐Fen Lin; Shih‐Chieh Hsu; Kuo‐Yen Wei; Ping‐Yu Chang; Pai‐Sen Yu (Journal of Quaternary Science, 2012)
The purpose of this study is to improve prehistoric knowledge of paleo‐typhoon and winter monsoon activity in the western North Pacific after 8 cal. ka BP. We examine two sediment cores derived from lakes located to the south and north of the Ilan Plain in northeastern Taiwan. Seasonal and typhoon rainfall data over the past several decades are collected for this study region. We also use mineral indicators, K/Rb ratios and grain size to estimate sediment sources, intensity of chemical weathering and rainfall intensity. The results show that the chemical weathering index (K/Rb ratio) of Meihua Lake indicates the continuing effects of autumn rainfall, while coarse grain sizes of Dahu Lake sediments suggest increased intensity in typhoon rainfall. Grain size results reveal that increasing El Niño–Southern Oscillation intensity in the tropical Pacific has intensified the activity of super typhoons in the western North Pacific. Finally, we find that frequent activity of super paleo‐typhoons occurred in Taiwan during the La Niña‐like state, and the strengthening winter monsoon activity and higher sea surface temperature enhanced plentiful autumn rainfall in El Niño‐like state. After comparing our results with the paleo‐typhoon data in Japan and south China, we suggest that the tracks of super typhoon are mainly affected by variations in the warm pool and subtropical Northwestern Pacific High in the western Pacific. Copyright © 2012 John Wiley & Sons, Ltd.

Lipoxin A4 Inhibits 5-Lipoxygenase Translocation and Leukotrienes Biosynthesis to Exert a Neuroprotective Effect in Cerebral Ischemia/Reperfusion Injury - Le Wu; Sen Miao; Lin-Bing Zou; Ping Wu; Hua Hao; Ke Tang; Pan Zeng; Jing Xiong; Hong-Hua Li; Qiang Wu; Lei Cai; Du-Yun Ye (Journal of Molecular Neuroscience, 2012)

Pollution and variation of stream nitrate in a protected high-mountain watershed of Central Taiwan: evidence from nitrate concentration and nitrogen and oxygen isotope compositions - Tsung-Ren Peng; Hsing-Juh Lin; Chung-Ho Wang; Tsang-Sen Liu; Shuh-Ji Kao (Environmental Monitoring and Assessment, 2012)

Endothelin-induced differentiation of Nkx2.5+ cardiac progenitor cells into pacemaking cells - Xi Zhang; Jin-Ping Guo; Ya-Li Chi; Yan-Chun Liu; Chuan-Sen Zhang; Xiang-Qun Yang; Hai-Yan Lin; Er-Peng Jiang; Shao-Hu Xiong; Zhi-Ying Zhang; Bao-Hai Liu (Molecular and Cellular Biochemistry, 2012)

Noninvasive Measurements of Cerebral Blood Flow, Oxygen Extraction Fraction, and Oxygen Metabolic Index in Human with Inhalation of Air and Carbogen using Magnetic Resonance Imaging - Hongyu An; Souvik Sen; Yasheng Chen; William J. Powers; Weili Lin (Translational Stroke Research, 2012)

Quercetin modulates activities of Taiwan cobra phospholipase A2 via its effects on membrane structure and membrane-bound mode of phospholipase A2 - Yi-Ling Chiou; Shinne-Ren Lin; Wan-Ping Hu; Long-Sen Chang (Journal of Biosciences, 2012)

Growth and union acclimation process of sweet pepper grafted by a tubing-grafting robotic system - Yung-Chiung Chang; Suming Chen; Yi-Chich Chiu; Lian-Hsiung Lin; Yu-Sen Chang (Horticulture, Environment, and Biotechnology, 2012)

Acute effects of plyometric jumping and intermittent running on serum bone markers in young males - Che-Fu Lin; Tsang-hai Huang; Kuo-Cheng Tu; Linda L. Lin; Yi-Hsuan Tu; Rong-Sen Yang (European Journal of Applied Physiology, 2012)

Interleukin 29 enhances expression of toll receptor 3 and mediates antiviral signals in human keratinocytes - Sheng-Quan Zhang; Zheng Zhang; Xin Luo; Sen Yang; Yu Chai; Hai-Liang Huang; Xian-Yong Yin; Dao-Jun Hu; Chun-Jun Yang; Jun-Lin Liu; Xue-Jun Zhang (Inflammation Research, 2011)

Numerical experiments investigating the orographic effects on a heavy rainfall event over the northwestern coast of Taiwan during TAMEX IOP 13 - Pay-Liam Lin; Yi-Leng Chen; Ching-Sen Chen; Che-Ling Liu; Ching-Ying Chen (Meteorology and Atmospheric Physics, 2011)

Role of high zinc levels in the stress defense of common carp - Tzu-Yung Lin; Yen-Hua Chen; Chien-Lin Liu; Sen-Shyong Jeng (Fisheries Science, 2011)

Bacteria associated with an encrusting sponge ( Terpios hoshinota ) and the corals partially covered by the sponge - Sen‐Lin Tang; Mei‐Jhu Hong; Ming‐Hui Liao; Wann‐Neng Jane; Pei‐Wen Chiang; Chung‐Bin Chen; Chaolun A. Chen (Environmental Microbiology, 2011)
Summary Terpios hoshinota , a dark encrusting sponge, is known to be a competitor for space in coral reef environments, and facilitates the death of corals. Although numerous cyanobacteria have been detected in the sponge, little is known of the sponge‐associated bacterial community. This study examined the sponge‐associated bacterial community and the difference between the bacterial communities in the sponge and the coral partially covered by the sponge by analysis of 16S rRNA gene sequences of samples isolated from the sponge covering the corals Favia complanata, Isopora palifera, Millepora sp. , Montipora efflorescens and Porites lutea . The sponge‐associated bacterial community was mainly (61–98%) composed of cyanobacteria, with approximately 15% of these alphaproteobacteria and gammaproteobacteria, although the proportions varied in different sponge samples. The dominant cyanobacteria group was an isolated group closely related to Prochloron sp. The comparison of the bacterial communities isolated from sponge‐free and the sponge‐covered P. lutea showed that covering by the sponge caused changes in the coral‐associated bacterial communities, with the presence of bacteria similar to those detected in black‐band disease, suggesting the sponge might benefit from the presence of bacteria associated with unhealthy coral, particularly in the parts of the coral closest to the margin of the sponge.

A broad-spectrum, efficient and nontransgenic approach to control plant viruses by application of salicylic acid and jasmonic acid - Jing Shang; De-Hui Xi; Fei Xu; Shao-Dong Wang; Sen Cao; Mo-Yun Xu; Ping-Ping Zhao; Jian-Hui Wang; Shu-Dan Jia; Zhong-Wei Zhang; Shu Yuan; Hong-Hui Lin (Planta, 2011)

Three novel SNPs in the coding region of PPARγ gene and their associations with meat quality traits in cattle - Yue Yuan Fan; Lin Sen Zan; Chang Zhen Fu; Wan Qiang Tian; Hong Bao Wang; Yan Yan Liu; Ya Ping Xin (Molecular Biology Reports, 2011)

Guanidination of notexin alters its membrane-damaging activity in response to sphingomyelin and cholesterol - Pei-Hsiu Kao; Yi-Ling Chiou; Shinne-Ren Lin; Long-Sen Chang (Journal of Biosciences, 2010)

Th17 promotes acute rejection following liver transplantation in rats - Xiao-jun Xie; Yu-fu Ye; Lin Zhou; Hai-yang Xie; Guo-ping Jiang; Xiao-wen Feng; Yong He; Qin-fen Xie; Shu-sen Zheng (Journal of Zhejiang University-SCIENCE B, 2010)

On the conservation biology of a Chinese population of the birdwing Troides aeacus (Lepidoptera: Papilionidae) - Xiu-shan Li; You-qing Luo; Ya-lin Zhang; Oliver Schweiger; Josef Settele; Qing-sen Yang (Journal of Insect Conservation, 2010)

A novel polymorphism of GDF5 gene and its association with body measurement traits in Bos taurus and Bos indicus breeds - Yong Feng Liu; Lin Sen Zan; Kui Li; Shuan Ping Zhao; Ya Ping Xin; Qing Lin; Wan Qiang Tian; Zhi Wei Wang (Molecular Biology Reports, 2010)

Cloning and Characterization of ApRab4, a Recycling Rab Protein of Aiptasia pulchella, and Its Implication in the Symbiosome Biogenesis - Ming-Cheng Hong; Yung-Sen Huang; Pa-Ching Song; Wen-Wen Lin; Lee-Shing Fang; Ming-Chyuan Chen (Marine Biotechnology, 2009)

Numerical simulations of flow motion and deposition characteristics of granular debris flows - Der-Guey Lin; Sen-Yen Hsu; Kuang-Tsung Chang (Natural Hazards, 2009)

Changes in estrogen receptor-α variant (ER-α36) expression during mouse ovary development and oocyte meiotic maturation - Bao-Zeng Xu; Sheng-Li Lin; Mo Li; Jia-Qiao Zhu; Sen Li; Ying-Chun Ouyang; Da-Yuan Chen; Qing-Yuan Sun (Histochemistry and Cell Biology, 2009)

Anoxia survival in common carp and crucian carp is related to high zinc concentration in tissues - Sen Shyong JENG; Tzu Yung LIN; Ming Shyong WANG; Yu Yin CHANG; Chao Yi CHEN; Chih Chieh CHANG (Fisheries Science, 2008)

Purification and characterization of a novel neutral β-glucanase and an alkaline β-glucanase from an alkaliphilic Bacillus isolate - Sen-Lin Liu; Wei-Zhao Chen; Yong Wang; Gang Liu; Shao-Wen Yu; Miao Xing (World Journal of Microbiology and Biotechnology, 2008)

Using SSR markers to determine the population genetic structure of wild apricot (Prunus armeniaca L.) in the Ily Valley of West China - He Tian-Ming; Chen Xue-Sen; Xu Zheng; Gao Jiang-Sheng; Lin Pei-Jun; Liu Wen; Liang Qing; Wu Yan (Genetic Resources and Crop Evolution, 2007)

High zinc in the erythrocyte plasma membranes of common carp Cyprinus carpio - Sen-Shyong JENG; Jeng-Yeng YAU; Yen-Hua CHEN; Tzu-Yung LIN; Yueh-Ying CHUNG (Fisheries Science, 2007)

Growth mechanism of a preferentially oriented mordenite membrane - Gang Li; Rui-sen Lin; Eiichi Kikuchi; Masahiko Matsukata (Journal of Zhejiang University-SCIENCE B, 2005)

Effect of dietary lipid level on growth performance, feed utilization and body composition of grouper Epinephelus coioides juveniles fed isonitrogenous diets in floating netcages - ZHI LUO; Yong-Jian Liu; Kang-Sen Mai; Li-Xia Tian; Dong-Hui Liu; Xiao-Ying Tan; Hei-Zhao Lin (Aquaculture International, 2005)

Synthesis of (R)-2-trimethylsilyl-2-hydroxyl-ethylcyanide catalyzed with (R)-oxynitrilase from loquat seed meal - Shun-Rong Huang; Sen-Lin Liu; Min-Hua Zong; Ruo Xu (Biotechnology Letters, 2005)

Molecular Cloning and Evolution of the Genes Encoding the Precursors of Taiwan Cobra Cardiotoxin and Cardiotoxin-Like Basic Protein - Long-Sen Chang; Shu-Kai Lin; Charling Chung (Biochemical Genetics, 2004)

Antitermitic and Antifungal Activities of Essential Oil of Calocedrus formosana Leaf and Its Composition - Sen-Sung Cheng; Chi-Lin Wu; Hui-Ting Chang; Yu-Ting Kao; Shang-Tzen Chang (Journal of Chemical Ecology, 2004)

Nitric oxide is not involved in the endotoxemia-induced alterations in Ca 2+ and ryanodine responses in mouse diaphragms - Shing-Hwa Liu; Jiun-Li Lai; Rong-Sen Yang; Shoei-Yn Lin-Shiau (Naunyn-Schmiedeberg's Archives of Pharmacology, 2002)

Evolution of DNA Polymerase Families: Evidences for Multiple Gene Exchange Between Cellular and Viral Proteins - Jonathan Filée; Patrick Forterre; Tang Sen-Lin; Jacqueline Laurent (Journal of Molecular Evolution, 2002)

Organization and Phylogenetic Analysis of κ-Bungarotoxin Genes from Bungarus Multicinctus (Taiwan Banded Krait) - Long-sen Chang; Charling Chung; Jordge Lin; Enjong Hong (Genetica, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)